Resin composition

JP2025036248APending Publication Date: 2025-03-14AJINOMOTO CO INC

Patent Information

Application Number
JP2024144197
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-01
Filing Date
2024-08-26
Publication Date
2025-03-14

AI Technical Summary

Benefits of technology

【0008】 本発明によれば、表面の平坦性、及び、めっき密着性に優れた絶縁層を得ることができ、かつ、回路基板における伝送損失を低減できる樹脂組成物及びシート状積層材料、並びに、伝送損失が低減された回路基板及び半導体装置を提供できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025036248000001
    Figure 2025036248000001
  • Figure 2025036248000002
    Figure 2025036248000002
  • Figure 2025036248000003
    Figure 2025036248000003
Patent Text Reader

Abstract

To provide a resin composition capable of obtaining an insulation layer excellent in smoothness of a surface, and plating adhesion property, and capable of reducing transmission loss in a circuit board.SOLUTION: A resin composition includes (A) epoxy resin, (B) hardener, (C) hollow inorganic filler, and (D) imidazole-based curing accelerator, where the porosity of (C) hollow inorganic filler is 40 volume% or more, an active region of (D) imidazole-based curing accelerator includes 130°C, (i) a reaction rate of (A) epoxy resin after performing the first stage of thermal curing at a curing temperature of less than 150°C is between 15% and 70%, and (ii) the reaction rate of (A) epoxy resin after performing the second stage of thermal curing at a curing temperature of 150°C or higher is 85% or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition. The present invention further relates to a sheet-like laminate material, a circuit board, and a semiconductor device each including a resin composition layer containing the resin composition. [Background technology]

[0002] In recent years, there has been a demand for miniaturization of electronic devices, faster signal speeds, and higher density wiring on circuit boards. Accordingly, there has been an increasing demand for lowering the dielectric constant of the insulating layer of the circuit board, improving the flatness of the insulating layer surface, and improving plating adhesion. For example, in order to reduce the relative dielectric constant of the insulating layer of the circuit board, Patent Documents 1 and 2 have considered an insulating layer using a resin composition containing a hollow inorganic filler such as hollow silica. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Patent No. 5864299 [Patent Document 2] Patent No. 7020378 Summary of the Invention [Problem to be solved by the invention]

[0004] However, if a hollow inorganic filler with a high porosity, for example 40% by volume or more, is used to reduce the relative dielectric constant of the insulating layer of the circuit board, the hollow inorganic filler is likely to crack during the process of thermally curing the resin composition to form the insulating layer, which increases the possibility of reducing the flatness of the insulating layer and reducing plating adhesion. In addition, since the content of the hollow inorganic filler in the resin composition cannot be increased, the relative dielectric constant of the insulating layer cannot be effectively reduced, making it difficult to reduce the transmission loss in the circuit board.

[0005] The present invention has been devised in view of the above-mentioned problems, and has an object to provide a resin composition and laminate that can obtain an insulating layer having excellent surface flatness and plating adhesion and can reduce transmission loss in a circuit board, as well as a circuit board and a semiconductor device with reduced transmission loss. [Means for solving the problem]

[0006] As a result of intensive research into solving the above-mentioned problems, the present inventors have found that the above-mentioned problems can be solved by using a hollow inorganic filler having a high porosity of 40 volume% or more and a curing accelerator having a specific active region, and further by controlling the reaction rate of the epoxy resin in the first and second heat curing stages within a predetermined range, thereby completing the present invention.

[0007] That is, the present invention includes the following. [1] A resin composition comprising (A) an epoxy resin, (B) a curing agent, (C) a hollow inorganic filler, and (D) an imidazole-based curing accelerator, (C) the porosity of the hollow inorganic filler is 40% by volume or more; (D) The active region of the imidazole curing accelerator includes 130° C. The resin composition has a reaction rate of 15% or more and 70% or less of the epoxy resin (A) after a first stage of heat curing at a curing temperature of less than 150°C, and a reaction rate of 85% or more of the epoxy resin (A) after a second stage of heat curing at a curing temperature of 150°C or more. [2] (D) Imidazole curing accelerator has the formula (1): [ka] [In the formula, R 1 represents a hydrogen atom or an alkyl group which may have a substituent, R 2 represents an alkyl group or a phenyl group, R 3 and R 4 each independently represents a hydrogen atom or an alkyl group. The resin composition according to [1], comprising a compound having a structure represented by the following formula: [3] The resin composition according to [1] or [2], wherein the imidazole curing accelerator (D) contains any one of compounds having structures represented by formulas (1-1) to (1-6) and an adduct of a compound having a structure represented by formula (1-7) and a compound having a structure represented by formula (2). [ka] [ka] [ka] [ka] [ka] [ka] [ka] [ka] [4] The resin composition according to any one of [1] to [3], further comprising (C') a solid inorganic filler. [5] The resin composition according to any one of [1] to [4], further comprising (E) a stress relaxation agent. [6] A sheet-like laminate material comprising a support and a resin composition layer provided on the support, the resin composition layer comprising the resin composition according to any one of [1] to [5]. [7] A circuit board comprising a cured product of the resin composition according to any one of [1] to [5]. [8] A semiconductor device comprising the circuit board according to [7]. Effect of the Invention

[0008] According to the present invention, it is possible to provide a resin composition and a sheet-like laminate material that can obtain an insulating layer having excellent surface flatness and plating adhesion and can reduce transmission loss in a circuit board, as well as a circuit board and a semiconductor device with reduced transmission loss. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] The present invention will be described in detail below with reference to preferred embodiments. However, the present invention is not limited to the following embodiments and examples, and can be modified and implemented as desired without departing from the scope of the claims of the present invention and their equivalents.

[0010] [Resin composition] The resin composition of the present invention comprises (A) an epoxy resin, (B) a curing agent, (C) a hollow inorganic filler, and (D) an imidazole-based curing accelerator, the porosity of the (C) hollow inorganic filler being 40% by volume or more, the active region of the (D) imidazole-based curing accelerator including 130° C., and the resin composition is (i) subjected to a first stage of thermal curing at a curing temperature of less than 150° C., after which the reaction rate of the (A) epoxy resin is 15% or more and 70% or less, and (ii) subjected to a second stage of thermal curing at a curing temperature of 150° C. or more, after which the reaction rate of the (A) epoxy resin is 85% or more. By using such a resin composition, an insulating layer having excellent surface flatness and plating adhesion can be obtained, and the transmission loss in the circuit board can be reduced.

[0011] The resin composition has a reaction rate of 15% or more and 70% or less, preferably 20% or more and 60% or less, more preferably 30% or more and 55% or less, and particularly preferably 40% or more and 50% or less, of the epoxy resin (A) after the first stage of heat curing at a curing temperature of less than 150 ° C. For example, when the reaction rate of the epoxy resin (A) after the first stage of heat curing of the resin composition is less than 15%, the hollow inorganic fillers collide with each other and tend to burst when the resin composition is subjected to a second stage of heat curing at a curing temperature of 150 ° C. or more, so that the flatness of the surface of the cured product of the resin composition (specifically, the insulating layer) is reduced. In addition, when the reaction rate of the epoxy resin (A) after the first stage of heat curing is 70% or more, the adhesion (so-called plating adhesion) of the cured product of the resin composition (insulating layer) to the plated conductor layer (e.g., copper plated conductor layer) is reduced.

[0012] The resin composition (ii) has a reaction rate of the epoxy resin (A) after a second-stage thermal curing at a curing temperature of 150°C or higher of 85% or more, preferably 90% or more, more preferably 92% or more, and particularly preferably 95% or more.

[0013] The resin composition may contain, in addition to (A) an epoxy resin, (B) a curing agent, (C) a hollow inorganic filler, and (D) an imidazole-based curing accelerator, for example, (C') a solid inorganic filler, (E) a stress relaxation component, (F) a dimer acid skeleton-containing component, (G) a thermoplastic resin, (H) other additives, and (I) an organic solvent, etc. Each component that may be contained in the resin composition will be described in detail below.

[0014] <(A) Epoxy resin> The resin composition of the present invention contains an epoxy resin (A). By containing the epoxy resin (A) in the resin composition, a cured product exhibiting good mechanical strength and insulation reliability can be obtained. The epoxy resin (A) may be used alone or in combination of two or more kinds.

[0015] Examples of the epoxy resin (A) include bixylenol type epoxy resin, bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol S type epoxy resin, bisphenol AF type epoxy resin, dicyclopentadiene type epoxy resin, trisphenol type epoxy resin, naphthol novolac type epoxy resin, phenol novolac type epoxy resin, tert-butyl-catechol type epoxy resin, naphthalene type epoxy resin, naphthol type epoxy resin, anthracene type epoxy resin, glycidylamine type epoxy resin, glycidyl ester type Examples of the epoxy resin include epoxy resins, glycidyl cyclohexane type epoxy resins, alkyl diglycidyl ether type epoxy resins, cresol novolac type epoxy resins, biphenyl type epoxy resins, linear aliphatic epoxy resins, epoxy resins having a butadiene structure, alicyclic epoxy resins, heterocyclic epoxy resins, spiro ring-containing epoxy resins, cyclohexane type epoxy resins, cyclohexane dimethanol type epoxy resins, naphthylene ether type epoxy resins, trimethylol type epoxy resins, tetraphenylethane type epoxy resins, phenolphthalimidine type epoxy resins, etc. The epoxy resins may be used alone or in combination of two or more.

[0016] The resin composition preferably contains, as the epoxy resin (A), an epoxy resin having two or more epoxy groups in one molecule. From the viewpoint of significantly obtaining the desired effects of the present invention, the proportion of the epoxy resin having two or more epoxy groups in one molecule relative to 100% by mass of the epoxy resin (A) is preferably 50% by mass or more, more preferably 60% by mass or more, and particularly preferably 70% by mass or more.

[0017] Epoxy resins include epoxy resins that are liquid at a temperature of 20° C. (hereinafter sometimes referred to as "liquid epoxy resins") and epoxy resins that are solid at a temperature of 20° C. (hereinafter sometimes referred to as "solid epoxy resins"). The resin composition may contain only a liquid epoxy resin as the epoxy resin (A), may contain only a solid epoxy resin, or may contain a combination of a liquid epoxy resin and a solid epoxy resin. Of these, from the viewpoint of achieving a remarkable effect of the present invention, it is preferable to contain a combination of a liquid epoxy resin and a solid epoxy resin.

[0018] The liquid epoxy resin is preferably a liquid epoxy resin having two or more epoxy groups in one molecule.

[0019] As the liquid epoxy resin, bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol AF type epoxy resin, naphthalene type epoxy resin, glycidyl ester type epoxy resin, glycidyl amine type epoxy resin, phenol novolac type epoxy resin, alicyclic epoxy resin having an ester skeleton, cyclohexane type epoxy resin, cyclohexane dimethanol type epoxy resin, glycidyl amine type epoxy resin, and epoxy resin having a butadiene structure, glycidyl cyclohexane type epoxy resin, phenolphthalimidine type epoxy resin, and alkyl diglycidyl ether type epoxy resin are preferred, bisphenol A type epoxy resin, bisphenol F type epoxy resin, and alkyl diglycidyl ether type epoxy resin are more preferred, and bisphenol A type epoxy resin is even more preferred.

[0020] Specific examples of liquid epoxy resins include "HP4032", "HP4032D", and "HP4032SS" (naphthalene type epoxy resins) manufactured by DIC Corporation; "828US", "jER828EL", "825", and "Epikote 828EL" (bisphenol A type epoxy resins) manufactured by Mitsubishi Chemical Corporation; "jER807" and "1750" (bisphenol F type epoxy resins) manufactured by Mitsubishi Chemical Corporation; "jER152" (phenol novolac type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "630" and "630LSD" (glycidylamine type epoxy resins) manufactured by Mitsubishi Chemical Corporation; and "ZX1" manufactured by Nippon Steel Chemical & Material Co., Ltd. Examples of epoxy resins include "EX-721" (a mixture of bisphenol A type epoxy resin and bisphenol F type epoxy resin) manufactured by Nagase ChemteX Corporation, "Celloxide 2021P" (alicyclic epoxy resin having an ester skeleton) manufactured by Daicel Corporation, "PB-3600" (epoxy resin having a butadiene structure) manufactured by Daicel Corporation, "ZX1658" and "ZX1658GS" (liquid 1,4-glycidylcyclohexane type epoxy resin) manufactured by Nippon Steel Chemical & Material Corporation, and "YED216D" (alkyl diglycidyl ether type epoxy resin) manufactured by Mitsubishi Chemical Corporation. These may be used alone or in combination of two or more types.

[0021] As the solid epoxy resin, a solid epoxy resin having two or more epoxy groups in one molecule is preferable, a solid epoxy resin having three or more epoxy groups in one molecule is more preferable, and an aromatic solid epoxy resin having three or more epoxy groups in one molecule is even more preferable.

[0022] As the solid epoxy resin, bixylenol type epoxy resin, naphthalene type epoxy resin, naphthalene type tetrafunctional epoxy resin, cresol novolac type epoxy resin, dicyclopentadiene type epoxy resin, trisphenol type epoxy resin, naphthol type epoxy resin, biphenyl type epoxy resin, naphthylene ether type epoxy resin, anthracene type epoxy resin, bisphenol A type epoxy resin, bisphenol AF type epoxy resin, and tetraphenylethane type epoxy resin are preferred, and biphenyl type epoxy resin is more preferred.

[0023] Specific examples of solid epoxy resins include "HP4032H" (naphthalene type epoxy resin), "HP-4700", "HP-4710" (naphthalene type tetrafunctional epoxy resin), "N-690" (cresol novolac type epoxy resin), "N-695" (cresol novolac type epoxy resin), "HP-7200", "HP-7200HH", "HP-7200H" (dicyclopentadiene type epoxy resin), "EXA-7311", "EXA-7311-G3", "EXA-7311-G4", "EXA-7311-G4S", "HP6000", "HP6000L" (naphthylene ether type epoxy resin), and "EPPN-502H" (trisphenol type epoxy resin), "NC7000L" (naphthol novolac type epoxy resin), "NC3000H", "NC3000", "NC3000L" manufactured by Nippon Kayaku Co., Ltd. Examples of epoxy resins include "NC3100" (biphenyl type epoxy resin); "ESN475V" (naphthalene type epoxy resin) and "ESN485" (naphthol novolac type epoxy resin) manufactured by Nippon Steel Chemical & Material Co., Ltd.; "YL6121" (biphenyl type epoxy resin), "YX4000H", "YX4000HK" (bixylenol type epoxy resin), and "YX8800" (anthracene type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "PG-100" and "CG-500" manufactured by Osaka Gas Chemical Co., Ltd.; "YL7760" (bisphenol AF type epoxy resin), "YL7800" (fluorene type epoxy resin), "jER1010" (solid bisphenol A type epoxy resin), and "jER1031S" (tetraphenylethane type epoxy resin) manufactured by Mitsubishi Chemical Co., Ltd.; and "WHR-991S" (phenolphthalimidine type epoxy resin) manufactured by Nippon Kayaku Co., Ltd. These may be used alone or in combination of two or more.

[0024] When a liquid epoxy resin and a solid epoxy resin are used in combination as the (A) epoxy resin, the ratio by mass between them (liquid epoxy resin:solid epoxy resin) is preferably 1:0.1 to 1:20, more preferably 1:0.15 to 1:10, and particularly preferably 1:0.2 to 1:5. When the ratio by mass between the liquid epoxy resin and the solid epoxy resin is within this range, the desired effects of the present invention can be significantly obtained.

[0025] The epoxy equivalent of the (A) epoxy resin is preferably 50 g / eq. to 5000 g / eq., more preferably 50 g / eq. to 3000 g / eq., even more preferably 80 g / eq. to 2000 g / eq., and even more preferably 110 g / eq. to 1000 g / eq. Within this range, a cured product having sufficient crosslink density of the cured product of the resin composition can be obtained. The epoxy equivalent is the mass of an epoxy resin containing one equivalent of epoxy groups. This epoxy equivalent can be measured according to JIS K7236.

[0026] From the viewpoint of significantly obtaining the desired effects of the present invention, the weight average molecular weight (Mw) of the (A) epoxy resin is preferably 100 to 5000, more preferably 150 to 3000, and further preferably 200 to 1500. The weight average molecular weight of the epoxy resin is a polystyrene-equivalent weight average molecular weight measured by gel permeation chromatography (GPC).

[0027] The content of the epoxy resin (A) in the resin composition may be preferably 5% by mass or more, more preferably 10% by mass or more, even more preferably 15% by mass or more, and particularly preferably 20% by mass or more, based on 100% by mass of the non-volatile components in the resin composition, from the viewpoint of obtaining a cured product exhibiting good mechanical strength and insulation reliability. The upper limit of the content may be preferably 50% by mass or less, more preferably 40% by mass or less, even more preferably 30% by mass or less, and particularly preferably 25% by mass or less, based on 100% by mass of the non-volatile components in the resin composition.

[0028] In the present invention, unless otherwise specified, the content of each component in the resin composition is a value when the non-volatile components in the resin composition are 100 mass %, and the non-volatile components mean all non-volatile components in the resin composition excluding the solvent.

[0029] In addition, the content of the epoxy resin (A) in the resin composition may be preferably 30% by mass or more, more preferably 45% by mass or more, even more preferably 50% by mass or more, and particularly preferably 55% by mass or more, based on 100% by mass of the resin component in the resin composition, from the viewpoint of obtaining a cured product exhibiting good mechanical strength and insulation reliability. The upper limit of the content may be preferably 75% by mass or less, more preferably 70% by mass or less, and particularly preferably 65% ​​by mass or less, based on 100% by mass of the resin component in the resin composition.

[0030] The resin component refers to the non-volatile components constituting the resin composition excluding the inorganic filler described below.

[0031] <(B) Hardener> The resin composition of the present invention further contains a curing agent (B). The curing agent (B) may be used alone or in any combination of two or more. The curing agent (B) may have a function of reacting with the epoxy resin (A) to cure it.

[0032] The (B) curing agent is not particularly limited, but examples thereof include active ester curing agents, phenolic curing agents, carbodiimide curing agents, acid anhydride curing agents, amine curing agents, benzoxazine curing agents, cyanate ester curing agents, and thiol curing agents. The (B) curing agent preferably contains one or more curing agents selected from active ester curing agents and phenolic curing agents. From the viewpoint of further suppressing the dielectric tangent, it is particularly preferable that the (B) curing agent contains an active ester curing agent. In addition, from the viewpoint of further improving the curing property, it is particularly preferable that the (B) curing agent contains a phenolic curing agent.

[0033] As the active ester curing agent, generally, compounds having two or more highly reactive ester groups in one molecule, such as phenol esters, thiophenol esters, N-hydroxyamine esters, and esters of heterocyclic hydroxy compounds, are preferably used. The active ester compound is preferably one obtained by a condensation reaction between a carboxylic acid compound and / or a thiocarboxylic acid compound and a hydroxy compound and / or a thiol compound. In particular, from the viewpoint of improving heat resistance, an active ester compound obtained from a carboxylic acid compound and a hydroxy compound is preferred, and an active ester compound obtained from a carboxylic acid compound and an aromatic hydroxy compound is more preferred. As the carboxylic acid compound, either an aromatic carboxylic acid compound or an aliphatic carboxylic acid compound may be used, and examples thereof include benzoic acid, acetic acid, succinic acid, maleic acid, itaconic acid, phthalic acid, isophthalic acid, terephthalic acid, pyromellitic acid, and halides thereof. Examples of aromatic hydroxy compounds include (i) polyaddition products of unsaturated aliphatic cyclic compounds containing two double bonds in one molecule and phenols, (ii) various bisphenol compounds, (iii) aromatic polyols having two or more hydroxyl groups bonded to the carbon atoms on the aromatic ring, and (iv) aromatic monools having one hydroxyl group bonded to the carbon atoms on the aromatic ring. Examples of polyaddition products of unsaturated aliphatic cyclic compounds and phenols include polyaddition products of unsaturated aliphatic cyclic compounds such as dicyclopentadiene, tetrahydroindene, norbornadiene, limonene, and vinylcyclohexene with phenols that may have a substituent (e.g., phenol, cresol, xylenol, ethylphenol, propylphenol, vinylphenol, allylphenol, phenylphenol, benzylphenol, halophenol, etc.), and specifically, for example, dicyclopentadiene-phenols polyaddition products. Examples of bisphenol compounds include bisphenol A, bisphenol F, bisphenol AF, bisphenol AP, bisphenol B, bisphenol BP, bisphenol C, and bisphenol M.Examples of aromatic polyols having two or more hydroxyl groups bonded to a carbon atom on an aromatic ring include hydroquinone, resorcinol, catechol, 1,5-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 2,6-dihydroxynaphthalene, dihydroxybenzophenone, trihydroxybenzophenone, tetrahydroxybenzophenone, phloroglucinol, benzenetriol, phenol novolak, etc. Examples of aromatic monools having one hydroxyl group bonded to a carbon atom on an aromatic ring include phenol, cresol, xylenol, ethylphenol, propylphenol, vinylphenol, allylphenol, phenylphenol, benzylphenol, halophenol, naphthol, methylnaphthol, dimethylnaphthol, ethylnaphthol, propylnaphthol, vinylnaphthol, allylnaphthol, phenylnaphthol, benzylnaphthol, halonaphthol, etc.

[0034] As the active ester curing agent, specifically, a dicyclopentadiene type active ester compound, a naphthalene type active ester compound containing a naphthalene structure, an active ester compound containing an acetylated product of phenol novolac, and an active ester compound containing a benzoylated product of phenol novolac are preferred, among which at least one selected from a dicyclopentadiene type active ester compound and a naphthalene type active ester compound is more preferred, and a dicyclopentadiene type active ester compound is even more preferred. As the dicyclopentadiene type active ester compound, an active ester compound containing a dicyclopentadiene type diphenol structure is preferred.

[0035] Commercially available active ester curing agents include active ester compounds containing a dicyclopentadiene-type diphenol structure, such as "EXB9451", "EXB9460", "EXB9460S", "HPC-8000L-65TM", "HPC-8000-65T", "HPC-8000H", and "HPC-8000H-65TM" (manufactured by DIC Corporation); and active ester compounds containing a naphthalene structure, such as "HP-B-8151-62T", "EXB-8100L-65T", "EXB-9416-70BK", and "HPC-8150-62T". and "EXB-8" (manufactured by DIC Corporation); an active ester compound containing phosphorus, "EXB9401" (manufactured by DIC Corporation), an active ester compound which is an acetylated product of phenol novolac, "DC808" (manufactured by Mitsubishi Chemical Corporation), active ester compounds which are benzoylated products of phenol novolac, "YLH1026", "YLH1030", and "YLH1048" (manufactured by Mitsubishi Chemical Corporation), and an active ester compound containing a styryl group and a naphthalene structure, "PC1300-02-65MA" (manufactured by Air Water Corporation), etc.

[0036] As the phenol-based curing agent, from the viewpoint of heat resistance and water resistance, a phenol-based curing agent having a novolac structure is preferable. Also, from the viewpoint of adhesion to the adherend, a nitrogen-containing phenol-based curing agent is preferable, and a triazine skeleton-containing phenol-based curing agent is more preferable. Among them, from the viewpoint of highly satisfying heat resistance, water resistance, and adhesion, a triazine skeleton-containing phenol novolac resin is preferable. Specific examples of phenol-based curing agents include "MEH-7700", "MEH-7810", and "MEH-7851" manufactured by Meiwa Kasei Co., Ltd.; "NHN", "CBN", and "GPH" manufactured by Nippon Kayaku Co., Ltd.; "SN-170", "SN-180", "SN-190", "SN-475", "SN-485", "SN-495", "SN-375", and "SN-395" manufactured by Nippon Steel Chemical & Material Co., Ltd.; and "LA-7052", "LA-7054", "LA-3018", "LA-3018-50P", "LA-1356", "TD2090", and "KA-1160" manufactured by DIC Corporation.

[0037] Examples of the carbodiimide-based curing agent include curing agents having one or more, preferably two or more, carbodiimide structures in one molecule, such as aliphatic biscarbodiimides, such as tetramethylene-bis(t-butylcarbodiimide) and cyclohexane bis(methylene-t-butylcarbodiimide); aromatic biscarbodiimides, such as phenylene-bis(xylylcarbodiimide); and aliphatic polycarbodiimides, such as polyhexamethylenecarbodiimide, polytrimethylhexamethylenecarbodiimide, polycyclohexylenecarbodiimide, poly(methylenebiscyclohexylenecarbodiimide), and poly(isophoronecarbodiimide). ; polycarbodiimides such as aromatic polycarbodiimides such as poly(phenylenecarbodiimide), poly(naphthylenecarbodiimide), poly(tolylenecarbodiimide), poly(methyldiisopropylphenylenecarbodiimide), poly(triethylphenylenecarbodiimide), poly(diethylphenylenecarbodiimide), poly(triisopropylphenylenecarbodiimide), poly(diisopropylphenylenecarbodiimide), poly(xylylenecarbodiimide), poly(tetramethylxylylenecarbodiimide), poly(methylenediphenylenecarbodiimide), and poly[methylenebis(methylphenylene)carbodiimide].

[0038] Commercially available carbodiimide curing agents include, for example, "Carbodilite V-02B", "Carbodilite V-03", "Carbodilite V-04K", "Carbodilite V-07", and "Carbodilite V-09" manufactured by Nisshinbo Chemical Co., Ltd.; and "Stavaxol P", "Stavaxol P400", and "Hi-Kasil 510" manufactured by LANXESS AG.

[0039] Examples of the acid anhydride curing agent include a curing agent having one or more acid anhydride groups in one molecule, and a curing agent having two or more acid anhydride groups in one molecule is preferable. Specific examples of the acid anhydride curing agent include phthalic anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, methylnadic anhydride, hydrogenated methylnadic anhydride, trialkyltetrahydrophthalic anhydride, dodecenyl succinic anhydride, 5-(2,5-dioxotetrahydro-3-furanyl)-3-methyl-3-cyclohexene-1,2-dicarboxylic anhydride, trimellitic anhydride, pyromellitic anhydride, benzophenonetetracarboxylic dianhydride, and the like. Examples of acid anhydrides include anhydrides, biphenyltetracarboxylic dianhydride, naphthalenetetracarboxylic dianhydride, oxydiphthalic dianhydride, 3,3'-4,4'-diphenylsulfonetetracarboxylic dianhydride, 1,3,3a,4,5,9b-hexahydro-5-(tetrahydro-2,5-dioxo-3-furanyl)-naphtho[1,2-C]furan-1,3-dione, ethylene glycol bis(anhydrotrimellitate), and polymeric acid anhydrides such as styrene-maleic acid resin, which is a copolymer of styrene and maleic acid. Commercially available acid anhydride curing agents include "HNA-100", "MH-700", "MTA-15", "DDSA", and "OSA" manufactured by New Japan Chemical Co., Ltd., "YH-306" and "YH-307" manufactured by Mitsubishi Chemical Corporation, "HN-2200" and "HN-5500" manufactured by Resonaq, and "EF-30", "EF-40", "EF-60", and "EF-80" manufactured by Cray Valley Chemical Industries, Ltd.

[0040] The amine-based curing agent may be a curing agent having one or more, preferably two or more, amino groups in one molecule, such as aliphatic amines, polyether amines, alicyclic amines, aromatic amines, etc., and among them, aromatic amines are preferred from the viewpoint of achieving the desired effects of the present invention. The amine-based curing agent is preferably a primary amine or secondary amine, and more preferably a primary amine. Specific examples of amine-based curing agents include 4,4'-methylenebis(2,6-dimethylaniline), 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenyl sulfone, 3,3'-diaminodiphenyl sulfone, m-phenylenediamine, m-xylylenediamine, diethyltoluenediamine, 4,4'-diaminodiphenyl ether, 3,3'-dimethyl-4,4'-diaminobiphenyl, 2,2'-dimethyl-4,4'-diaminobiphenyl, 3,3'-dihydroxybenzidine, and 2,2-bis(3-amino-4-hydroxyphenyl)propane. propane, 3,3-dimethyl-5,5-diethyl-4,4-diphenylmethanediamine, 2,2-bis(4-aminophenyl)propane, 2,2-bis(4-(4-aminophenoxy)phenyl)propane, 1,3-bis(3-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, 4,4'-bis(4-aminophenoxy)biphenyl, bis(4-(4-aminophenoxy)phenyl)sulfone, bis(4-(3-aminophenoxy)phenyl)sulfone, and the like. As the amine-based curing agent, commercially available products may be used, and examples thereof include "SEIKACURE-S" manufactured by Seika Corporation, "KAYABOND C-200S", "KAYABOND C-100", "KAYAHARD AA", "KAYAHARD AB", and "KAYAHARD AS" manufactured by Nippon Kayaku Co., Ltd., and "Epicure W" manufactured by Mitsubishi Chemical Corporation.

[0041] Specific examples of benzoxazine-based curing agents include "JBZ-OP100D" and "ODA-BOZ" manufactured by JFE Chemical Corporation; "HFB2006M" manufactured by Showa Polymer Co., Ltd.; and "Pd" and "Fa" manufactured by Shikoku Chemical Industry Co., Ltd.

[0042] Examples of the cyanate ester curing agent include bifunctional cyanate resins such as bisphenol A dicyanate, polyphenol cyanate (oligo(3-methylene-1,5-phenylene cyanate)), 4,4'-methylenebis(2,6-dimethylphenyl cyanate), 4,4'-ethylidene diphenyl dicyanate, hexafluorobisphenol A dicyanate, 2,2-bis(4-cyanate)phenylpropane, 1,1-bis(4-cyanate phenylmethane), bis(4-cyanate-3,5-dimethylphenyl)methane, 1,3-bis(4-cyanate phenyl-1-(methylethylidene))benzene, bis(4-cyanate phenyl)thioether, and bis(4-cyanate phenyl)ether; polyfunctional cyanate resins derived from phenol novolac and cresol novolac; and prepolymers in which these cyanate resins are partially converted to triazine. Specific examples of cyanate ester-based curing agents include "PT30" and "PT60" (both of which are phenol novolac-type multifunctional cyanate ester resins) manufactured by Arxada, "BA230" and "BA230S75" (prepolymers in which part or all of bisphenol A dicyanate has been converted to triazine to form a trimer).

[0043] Examples of thiol-based curing agents include trimethylolpropane tris(3-mercaptopropionate), pentaerythritol tetrakis(3-mercaptobutyrate), and tris(3-mercaptopropyl)isocyanurate.

[0044] The reactive group equivalent of the (B) curing agent is preferably 50 g / eq. to 3000 g / eq., more preferably 100 g / eq. to 1000 g / eq., further preferably 100 g / eq. to 500 g / eq., and particularly preferably 100 g / eq. to 300 g / eq. The reactive group equivalent is the mass of the (B) curing agent per equivalent of reactive group.

[0045] The molar ratio of the total epoxy groups of the epoxy resin (A) to the total reactive groups of the curing agent (B) in the resin composition (number of moles of epoxy groups: number of moles of reactive groups) is preferably within the range of 1:0.2 to 1:2, more preferably within the range of 1:0.3 to 1:1.5, and even more preferably within the range of 1:0.4 to 1:1.

[0046] The content of the (B) curing agent in the resin composition may be preferably 40% by mass or less, more preferably 30% by mass or less, even more preferably 20% by mass or less, and particularly preferably 15% by mass or less, when the non-volatile components in the resin composition are taken as 100% by mass. The lower limit of the content may be preferably 3% by mass or more, more preferably 5% by mass or more, even more preferably 8% by mass or more, and particularly preferably 10% by mass or more, when the non-volatile components in the resin composition are taken as 100% by mass.

[0047] The content of the (B) curing agent in the resin composition may be preferably 50% by mass or less, more preferably 45% by mass or less, even more preferably 40% by mass or less, and particularly preferably 35% by mass or less, when the resin component in the resin composition is taken as 100% by mass. The lower limit of the content may be preferably 15% by mass or more, more preferably 20% by mass or more, even more preferably 25% by mass or more, and particularly preferably 30% by mass or more, when the resin component in the resin composition is taken as 100% by mass.

[0048] When the (B) curing agent contains an active ester curing agent, the content of the active ester curing agent in the resin composition, when the non-volatile components in the resin composition are taken as 100% by mass, may be preferably 1% by mass or more, more preferably 3% by mass or more, even more preferably 5% by mass or more, and particularly preferably 7% by mass or more, from the viewpoint of suppressing the dielectric tangent to a lower level. In addition, when the (B) curing agent in the resin composition is taken as 100% by mass, the lower limit of the content of the active ester curing agent in the resin composition may be preferably 10% by mass or more, more preferably 30% by mass or more, even more preferably 40% by mass or more, and particularly preferably 50% by mass or more, from the viewpoint of suppressing the dielectric tangent to a lower level.

[0049] When the (B) curing agent contains a phenol-based curing agent, the content of the phenol-based curing agent in the resin composition, when the non-volatile components in the resin composition are taken as 100 mass%, may be preferably 0.5 mass% or more, more preferably 1 mass% or more, and particularly preferably 2 mass% or more, from the viewpoint of further improving curability, and the upper limit of the content may be 10 mass% or less, 5 mass% or less, etc.

[0050] <(C) Hollow inorganic filler> The resin composition of the present invention contains a hollow inorganic filler (C). The hollow inorganic filler (C) has a porosity of 40 volume % or more. The hollow inorganic filler (C) is contained in the resin composition in the form of particles. The hollow inorganic filler (C) may be used alone or in combination of two or more kinds in any ratio.

[0051] Examples of materials for forming the (C) hollow inorganic filler include silica, alumina, and aluminosilicates, with silica being preferred.

[0052] (C) The hollow inorganic filler has a void inside the particle. (C) The hollow inorganic filler may be a monohollow particle having only one void inside the particle, a polyhollow particle having two or more voids inside the particle, or a mixture thereof.

[0053] The porosity of the (C) hollow inorganic filler may be 40 vol% or more, preferably 45 vol% or more, more preferably 48 vol% or more, and particularly preferably 50 vol% or more in order to reduce transmission loss, and the upper limit may be preferably 90 vol% or less, more preferably 80 vol% or less, even more preferably 70 vol% or less, and particularly preferably 60 vol% or less in order to further improve mechanical strength.

[0054] The porosity P (volume %) of an inorganic filler is defined as the volume ratio of the total volume of one or more voids present inside the particle to the total volume of the particle based on the outer surface of the particle (total volume of voids / volume of particle). For example, the measured value of the actual density of the inorganic filler D M (g / cm 3), and the theoretical value of the material density of the material forming the inorganic filler D T (g / cm 3 ) is used to calculate the following formula (1).

[0055]

number

[0056] (C) hollow inorganic filler may be a commercially available product, or may be produced by a known method or a method equivalent thereto. (C) Commercially available hollow inorganic filler products include, for example, hollow silica "LHP-208" manufactured by Ube Exsymo Co., Ltd., hollow aluminosilicate particles "Cellspheres", "MGH-005", and "MG-005" manufactured by Taiheiyo Cement Corporation. Among them, hollow silica is more preferable because it is softer than hollow aluminosilicate particles, and therefore has a greater effect of alleviating stress accumulated during substrate production, and as a result, the effect of further improving adhesion to the conductor is obtained. Specific examples of the method for producing hollow inorganic filler are not particularly limited, but a method can be used in which an aqueous solution containing a substance capable of forming voids and a basic compound is prepared, the aqueous solution is mixed with an alkoxysilane, and stirred to precipitate silica particles, the substance capable of forming voids is removed from the silica particles to obtain a hollow silica precursor, and the obtained hollow silica precursor is fired.

[0057] The hollow inorganic filler (C) is preferably surface-heat-treated. The conditions for the surface heat treatment are not particularly limited, but from the viewpoint of suppressing breakage (fracture) due to collision between particles, the treatment temperature is, for example, in the range of 50°C to 100°C, preferably 70°C to 80°C, and the treatment time is, for example, in the range of 0.5 hours to 3 hours, preferably 1 hour to 3 hours.

[0058] (C) The hollow inorganic filler is preferably treated with a surface treatment agent from the viewpoint of improving moisture resistance and dispersibility. The treatment with the surface treatment agent is preferably carried out simultaneously with the heat treatment described above. Examples of the surface treatment agent include fluorine-containing silane coupling agents, aminosilane coupling agents, epoxysilane coupling agents, mercaptosilane coupling agents, silane coupling agents, alkoxysilanes, organosilazane compounds, titanate coupling agents, etc. Furthermore, the surface treatment agent may be used alone or in any combination of two or more types.

[0059] Examples of commercially available surface treatment agents include Shin-Etsu Chemical Co., Ltd.'s "KBM403" (3-glycidoxypropyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBM803" (3-mercaptopropyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBE903" (3-aminopropyltriethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBM573" (N-phenyl-3-aminopropyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "SZ-31" (hexamethyldisilazane), Shin-Etsu Chemical Co., Ltd.'s "KBM103" (phenyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBM-4803" (long-chain epoxy-type silane coupling agent), and Shin-Etsu Chemical Co., Ltd.'s "KBM-7103" (3,3,3-trifluoropropyltrimethoxysilane).

[0060] The degree of surface treatment with the surface treatment agent is preferably within a predetermined range from the viewpoint of improving the dispersibility of the hollow inorganic filler (C). Specifically, the surface treatment is preferably performed with 0.2% by mass to 5% by mass of the surface treatment agent relative to 100% by mass of the hollow inorganic filler (C), more preferably 0.2% by mass to 3% by mass, and even more preferably 0.3% by mass to 2% by mass.

[0061] The degree of surface treatment with a surface treatment agent can be evaluated by the amount of carbon per unit surface area of ​​the hollow inorganic filler. (C) The amount of carbon per unit surface area of ​​the hollow inorganic filler is set to 0.02 mg / m from the viewpoint of improving the dispersibility of the inorganic filler.2 More than 0.1 mg / m is preferable. 2 More preferably, 0.2 mg / m or more 2 On the other hand, from the viewpoint of preventing an increase in the melt viscosity of the resin composition or the melt viscosity in the form of a sheet, it is more preferable that the melt viscosity is 1.0 mg / m 2 Less than 0.8 mg / m is preferred. 2 Less than 0.5 mg / m is more preferable. 2 The following is more preferable. The amount of carbon per unit surface area of ​​the inorganic filler can be measured after the surface-treated inorganic filler is washed with a solvent (e.g., methyl ethyl ketone (MEK)). Specifically, a sufficient amount of MEK as a solvent is added to the inorganic filler that has been surface-treated with a surface treatment agent, and ultrasonic cleaning is performed at 25°C for 5 minutes. After removing the supernatant and drying the solid content, the amount of carbon per unit surface area of ​​the inorganic filler can be measured using a carbon analyzer. As the carbon analyzer, an "EMIA-320V" manufactured by Horiba, Ltd., or the like can be used.

[0062] The content of the hollow inorganic filler (C) in the resin composition may be preferably 50% by mass or less, more preferably 45% by mass or less, even more preferably 40% by mass or less, and particularly preferably 35% by mass or less, based on 100% by mass of the non-volatile components in the resin composition. From the viewpoint of obtaining the desired effects of the present invention more significantly, the lower limit of the content is preferably 5% by mass or more, more preferably 10% by mass or more, even more preferably 15% by mass or more, and particularly preferably 18% by mass or more, based on 100% by mass of the non-volatile components in the resin composition.

[0063] (C) The average particle size of the hollow inorganic filler may be 5.0 μm or less, preferably 4.0 μm or less, more preferably 3.0 μm or less, even more preferably 2.5 μm or less, even more preferably 2.2 μm or less, and particularly preferably 1.5 μm or less, from the viewpoint of obtaining the desired effect of the present invention more significantly. The lower limit of the average particle size may be preferably 0.3 μm or more, preferably 0.5 μm or more. The smaller the particle size, the less the number of collisions between particles, and by setting the degree of hardening of the present invention to an appropriate range, the effect of more excellent flatness can be obtained. The average particle size of the inorganic filler can be measured by a laser diffraction scattering method based on the Mie scattering theory. Specifically, the particle size distribution of the inorganic filler is created on a volume basis using a laser diffraction scattering type particle size distribution measuring device, and the median diameter is used as the average particle size. The measurement sample can be prepared by weighing 100 mg of the inorganic filler and 10 g of methyl ethyl ketone into a vial and dispersing it by ultrasonic waves for 10 minutes. The measurement sample was measured using a laser diffraction type particle size distribution measuring device with blue and red light source wavelengths, and the particle size distribution of the inorganic filler on a volume basis was measured using a flow cell method, and the average particle size was calculated as the median diameter from the particle size distribution obtained. An example of a laser diffraction type particle size distribution measuring device is the "LA-960" manufactured by Horiba, Ltd.

[0064] (C) The specific surface area of ​​the hollow inorganic filler is preferably 60 m 2 / g or less, more preferably 40m 2 / g or less, more preferably 20m 2 / g or less, particularly preferably 15m 2 The lower limit of the specific surface area is, for example, 1 m 2 The specific surface area of ​​the hollow inorganic filler can be obtained by adsorbing nitrogen gas onto the surface of a sample using a specific surface area measuring device (Macsorb HM-1210 manufactured by Mountech Co., Ltd.) according to the BET method, and calculating the specific surface area using the BET multipoint method.

[0065] <(C') Solid inorganic filler> The resin composition of the present invention may further contain a solid inorganic filler (C') as an optional component. When the solid inorganic filler (C') is contained, the solid inorganic filler (C') may be used alone or in combination of two or more kinds in any ratio.

[0066] As the material of the (C') solid inorganic filler, an inorganic compound is used. As the material of the (C') solid inorganic filler, for example, silica, alumina, glass, cordierite, silicon oxide, barium sulfate, barium carbonate, talc, clay, mica powder, zinc oxide, hydrotalcite, boehmite, aluminum hydroxide, magnesium hydroxide, calcium carbonate, magnesium carbonate, magnesium oxide, boron nitride, aluminum nitride, manganese nitride, aluminum borate, strontium carbonate, strontium titanate, calcium titanate, magnesium titanate, bismuth titanate, titanium oxide, zirconium oxide, barium titanate, barium zirconate titanate, barium zirconate, calcium zirconate, zirconium phosphate, and zirconium tungstate phosphate are listed. Among these, silica is particularly suitable. As the silica, for example, amorphous silica, fused silica, crystalline silica, synthetic silica, etc. are listed. In addition, as the (C') solid inorganic filler, spherical silica is preferable.

[0067] (C') Commercially available solid inorganic fillers include, for example, "SP60-05" and "SP507-05" manufactured by Nippon Steel Chemical & Material Co., Ltd.; "YC100C", "YA050C", "YA050C-MJE", "YA010C", "SC2500SQ", "SO-C4", "SO-C2", and "SO-C1" manufactured by Admatechs Co., Ltd.; "UFP-30", "DAW-03", and "FB-105FD" manufactured by Denka Co., Ltd.; and "Silfill NSS-3N", "Silfill NSS-4N", and "Silfill NSS-5N" manufactured by Tokuyama Corporation.

[0068] The average particle size of the (C') solid inorganic filler is not particularly limited, but is preferably 10 μm or less, more preferably 5 μm or less, even more preferably 3 μm or less, even more preferably 2 μm or less, and particularly preferably 1.5 μm or less. The lower limit of the average particle size is not particularly limited, but is preferably 0.01 μm or more, more preferably 0.05 μm or more, even more preferably 0.1 μm or more, and particularly preferably 0.2 μm or more.

[0069] The specific surface area of ​​the solid inorganic filler (C') is not particularly limited, but is preferably 0.1 m 2 / g or more, more preferably 0.5m 2 / g or more, more preferably 1m 2 / g or more, particularly preferably 3m 2 The upper limit of the specific surface area is not particularly limited, but is preferably 100 m 2 / g or less, more preferably 70m 2 / g or less, more preferably 50m 2 / g or less, and even more preferably 30m 2 / g or less, particularly preferably 10m 2 / g or less.

[0070] From the viewpoint of improving moisture resistance and dispersibility, the solid inorganic filler (C') is preferably treated with a surface treatment agent. As the surface treatment agent, the above-mentioned ones can be used, as in the hollow inorganic filler (C). The degree of surface treatment with the surface treatment agent and the amount of carbon per unit surface area can be the same as in the hollow inorganic filler (C).

[0071] The content of the (C') solid inorganic filler in the resin composition may be preferably 80% by mass or less, more preferably 70% by mass or less, even more preferably 60% by mass or less, even more preferably 50% by mass or less, and particularly preferably 48% by mass or less, when the nonvolatile components in the resin composition are taken as 100% by mass. The lower limit of the content may be, for example, 0% by mass or more, 5% by mass or more, preferably 10% by mass or more, more preferably 20% by mass or more, even more preferably 25% by mass or more, and particularly preferably 28% by mass or more, when the nonvolatile components in the resin composition are taken as 100% by mass.

[0072] The content of the hollow inorganic filler (C) relative to the total of the hollow inorganic filler (C) and the solid inorganic filler (C') (hereinafter referred to as inorganic filler) may be preferably 65% ​​by mass or less, more preferably 60% by mass or less, and particularly preferably 55% by mass or less, when the inorganic filler in the resin composition is taken as 100% by mass. The lower limit of the content may be preferably 10% by mass or more, more preferably 20% by mass or more, even more preferably 25% by mass or more, and particularly preferably 30% by mass or more.

[0073] The content of the (C') solid inorganic filler relative to the inorganic filler may be preferably 80% by mass or less, more preferably 75% by mass or less, and particularly preferably 70% by mass or less, based on 100% by mass of the inorganic filler in the resin composition. The lower limit of the content is preferably 20% by mass or more, more preferably 30% by mass or more, even more preferably 40% by mass or more, and particularly preferably 45% by mass or more.

[0074] The content of the inorganic filler in the resin composition may be preferably 80% by mass or less, more preferably 75% by mass or less, even more preferably 70% by mass or less, and particularly preferably 68% by mass or less, when the nonvolatile components in the resin composition are taken as 100% by mass. From the viewpoint of further suppressing the dielectric loss tangent and the relative dielectric constant, the lower limit of the content is preferably 30% by mass or more, more preferably 40% by mass or more, even more preferably 50% by mass or more, and particularly preferably 60% by mass or more, when the nonvolatile components in the resin composition are taken as 100% by mass.

[0075] <(D) Imidazole-based curing accelerator> The resin composition of the present invention contains (D) an imidazole-based curing accelerator. (D) The imidazole-based curing accelerator functions as a curing catalyst that accelerates the curing of (A) the epoxy resin. (D) The imidazole-based curing accelerator has an active range of 130°C. For example, when an imidazole-based curing accelerator whose active region does not include 130°C and has an active region lower than 130°C is used, the reaction rate of the epoxy resin (A) after the resin composition is subjected to the first-stage thermal curing at a curing temperature of less than 150°C becomes higher than 70%, and the adhesion (plating adhesion) of the cured product of the resin composition (insulating layer) to a plated conductor layer (e.g., a copper-plated conductor layer) decreases.

[0076] On the other hand, for example, when an imidazole-based curing accelerator whose active region does not include 130° C. and has an active region higher than 130° C. is used, the reaction rate of the epoxy resin (A) after the first stage of thermal curing of the resin composition at a curing temperature of less than 150° C. is lower than 15%. In this case, when the second stage of thermal curing of the resin composition is performed at a curing temperature of 150° C. or higher, the hollow inorganic fillers collide with each other and tend to burst, and the surface flatness of the cured product (insulating layer) of the resin composition is reduced.

[0077] In the present invention, the "active region" of the curing accelerator refers to a temperature region that is equal to or higher than the peak top temperature of the exothermic peak among the temperature regions that show an exothermic reaction when the exothermic behavior accompanying the curing during heating is measured by differential scanning calorimetry (DSC) for a mixture of 5 parts by mass of the curing accelerator and 100 parts by mass of a liquid bisphenol A type epoxy resin. For example, when the exothermic behavior of the curing accelerator X during heating is measured by DSC as described above, the temperature region showing the exothermic reaction is from 100°C to 180°C, and the peak top temperature of the exothermic peak is 120°C. In this case, the active region of the curing accelerator X is a temperature region from 120°C to 180°C, and the active region is determined to include 130°C. On the other hand, when the exothermic behavior of the curing accelerator Y during heating is measured by DSC as described above, the temperature region showing the exothermic reaction is from 100°C to 180°C, and the peak top temperature of the exothermic peak is 140°C. In this case, the active region of the curing accelerator Y is determined to be the temperature range from 140°C to 180°C, and the active region does not include 130°C.

[0078] As described above, when the exothermic behavior during heating is measured by DSC, the temperature region showing an exothermic reaction, which is below the peak top temperature of the exothermic peak, is also referred to as the "reaction initiation region".

[0079] (D) The imidazole curing accelerator is preferably represented by the formula (1):

[0080] [ka]

[0081] [In the formula, R 1 represents a hydrogen atom or an alkyl group which may have a substituent, R 2 represents an alkyl group or a phenyl group, R 3 and R 4 each independently represents a hydrogen atom or an alkyl group. The present invention includes compounds having a structure represented by the following formula:

[0082] The above "alkyl group" may be either linear or branched.

[0083] In this specification, the term "optionally having a substituent" in relation to a compound or group means both the case where the hydrogen atoms of the compound or group are not substituted with a substituent, and the case where some or all of the hydrogen atoms of the compound or group are substituted with a substituent.

[0084] In this specification, unless otherwise specified, the term "substituent" means a halogen atom, an alkenyl group, an alkynyl group, an alkapolyenyl group, a cycloalkyl group, a cycloalkenyl group, an alkoxy group, an alkenyloxy group, a cycloalkyloxy group, a cycloalkenyloxy group, an alkylthio group, a cycloalkylthio group, an aryl group, an aryloxy group, an arylthio group, an arylalkyl group, an arylalkoxy group, a heterocyclic group (the heterocyclic group may be further substituted with an amino group), an alkylidene group, an acyl group, an acyloxy group, an amino group, a silyl group, a carboxy group, a sulfo group, a cyano group, a nitro group, a mercapto group, or an oxo group.

[0085] Examples of halogen atoms used as a substituent include a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom. The alkyl group used as a substituent may be either linear or branched. The alkenyl group or alkynyl group used as a substituent may be either linear or branched. The number of carbon atoms in the alkenyl group or alkynyl group is preferably 2 to 12, more preferably 2 to 6, and even more preferably 2 or 3. The alkapolyenyl group used as a substituent may be either linear or branched, and the number of double bonds is preferably 2 to 10, more preferably 2 to 6, even more preferably 2 to 4, and even more preferably 2. The number of carbon atoms in the alkapolyenyl group is preferably 3 to 20, more preferably 3 to 14, even more preferably 3 to 12, and even more preferably 3 to 6. The number of carbon atoms in the cycloalkyl group or cycloalkenyl group used as a substituent is preferably 3 to 12, and more preferably 3 to 6. The alkoxy group used as a substituent may be either linear or branched. The number of carbon atoms in the alkoxy group is preferably 1 to 12, more preferably 1 to 6. The alkenyloxy group used as a substituent may be either linear or branched. The number of carbon atoms in the alkenyloxy group is preferably 2 to 12, more preferably 2 to 6, and even more preferably 2 or 3. The number of carbon atoms in the cycloalkyloxy group or cycloalkenyloxy group used as a substituent is preferably 3 to 12, more preferably 3 to 6. The alkylthio group used as a substituent may be either linear or branched. The number of carbon atoms in the alkylthio group is preferably 1 to 12, more preferably 1 to 6. The number of carbon atoms in the cycloalkylthio group used as a substituent is preferably 3 to 12, more preferably 3 to 6. The number of carbon atoms in the aryl group used as a substituent is preferably 6 to 14, more preferably 6 to 10. The number of carbon atoms in the aryloxy group used as a substituent is preferably 6 to 14, more preferably 6 to 10. The number of carbon atoms in the arylthio group used as a substituent is preferably 6 to 14, more preferably 6 to 10.The number of carbon atoms of the arylalkyl group used as a substituent is preferably 7 to 15, more preferably 7 to 11. The number of carbon atoms of the arylalkoxy group used as a substituent is preferably 7 to 15, more preferably 7 to 11. The heterocyclic group used as a substituent refers to a group obtained by removing one hydrogen atom from a heterocyclic compound. The number of carbon atoms of the heterocyclic group is preferably 3 to 15, more preferably 3 to 9. An example of the heterocyclic compound is 1,3,5-triazine. The alkylidene group used as a substituent refers to a group obtained by removing two hydrogen atoms from the same carbon atom of an alkane. The number of carbon atoms of the alkylidene group is preferably 1 to 12, more preferably 1 to 6, and particularly preferably 1 to 3. The acyl group used as a substituent is represented by the formula: -C(=O)-R. S (wherein R S R is an alkyl group. S The alkyl group represented by the formula: may be either linear or branched. The number of carbon atoms in the acyl group is preferably 2 to 13, more preferably 2 to 7. The acyloxy group used as a substituent is represented by the formula: -OC(=O)-R S (wherein R S is as defined above). The number of carbon atoms in the acyloxy group is preferably 2 to 13, more preferably 2 to 7. The above-mentioned substituent may further have a substituent (sometimes referred to as a "secondary substituent"). As the secondary substituent, unless otherwise specified, the same as the above-mentioned substituent may be used.

[0086] The (D) imidazole curing accelerator includes, for example, any of the compounds having the structure represented by formulas (1-1) to (1-6) and an adduct of a compound having the structure represented by formula (1-7) and a compound having the structure represented by formula (2). In one embodiment, the (D) imidazole curing accelerator may be an adduct of a compound having the structure represented by formula (1-7) and a compound having the structure represented by formula (2) (i.e., isocyanuric acid). [ka]

change

change

change

change

change

change

change

[0087] The active region of the (D) imidazole-based curing accelerator containing a compound having a structure represented by formula (1-1) is a temperature region from 103°C to 123°C, and is commercially available as "C17Z" (manufactured by Shikoku Chemical Industry Co., Ltd.). The active region of the (D) imidazole-based curing accelerator containing a compound having a structure represented by formula (1-2) is a temperature region from 107°C to 135°C, and is commercially available as "1B2MZ" (manufactured by Shikoku Chemical Industry Co., Ltd.). The active region of the (D) imidazole-based curing accelerator containing a compound having a structure represented by formula (1-3) is a temperature region from 104°C to 152°C, and is commercially available as "1B2PZ" (manufactured by Shikoku Chemical Industry Co., Ltd.). The active region of the (D) imidazole-based curing accelerator containing a compound having a structure represented by formula (1-4) is a temperature region from 117°C to 146°C, and is commercially available as "2MZ-CN" (manufactured by Shikoku Chemical Industry Co., Ltd.). The active region of the (D) imidazole-based curing accelerator containing a compound having a structure represented by formula (1-5) is a temperature region from 121°C to 150°C, and is commercially available as "2E4MZ-CN" (manufactured by Shikoku Chemical Industry Co., Ltd.). The active region of the (D) imidazole-based curing accelerator containing a compound having a structure represented by formula (1-6) is a temperature region from 128°C to 147°C, and is commercially available as "C11Z-A" (manufactured by Shikoku Chemical Industry Co., Ltd.). The active region of the (D) imidazole-based curing accelerator containing an adduct of a compound having a structure represented by formula (1-7) and a compound having a structure represented by formula (2) is a temperature region from 130°C to 147°C, and is commercially available as "2MA-OK" (manufactured by Shikoku Chemical Industry Co., Ltd.).

[0088] The content of the (D) imidazole curing accelerator in the resin composition may be preferably 0.4% by mass or less, more preferably 0.3% by mass or less, even more preferably 0.25% by mass or less, and particularly preferably 0.2% by mass or less, based on 100% by mass of the non-volatile components in the resin composition. The lower limit of the content in the resin composition may be preferably 0.03% by mass or more, more preferably 0.05% by mass or more, even more preferably 0.08% by mass or more, and particularly preferably 0.1% by mass or more, based on 100% by mass of the non-volatile components in the resin composition.

[0089] The content of the (D) imidazole curing accelerator in the resin composition may be preferably 0.8% by mass or less, more preferably 0.7% by mass or less, even more preferably 0.65% by mass or less, and particularly preferably 0.6% by mass or less, when the resin components in the resin composition are taken as 100% by mass. The lower limit of the content of the (D) imidazole curing accelerator in the resin composition is preferably 0.05% by mass or more, more preferably 0.1% by mass or more, even more preferably 0.15% by mass or more, and particularly preferably 0.2% by mass or more, when the non-volatile components in the resin composition are taken as 100% by mass.

[0090] The resin composition may contain a curing accelerator other than the (D) imidazole-based curing accelerator (hereinafter referred to as (D') other curing accelerator). The (D') other curing accelerator may be used in combination with the (D) imidazole-based curing accelerator, and the type is not particularly limited. Examples of the (D') other curing accelerator include imidazole-based curing accelerators whose active region does not include 130°C, phosphorus-based curing accelerators, urea-based curing accelerators, guanidine-based curing accelerators, metal-based curing accelerators, and amine-based curing accelerators. The (D') other curing accelerators may be used alone or in combination of two or more.

[0091] Examples of imidazole-based curing accelerators whose active region does not include 130°C include imidazole compounds such as 1-(2-cyanoethyl)-2-phenylimidazole, 1-(2-cyanoethyl)-2-phenylimidazolium trimellitate, 2,4-diamino-6-[2-(2-methylimidazol-1-yl)ethyl]-1,3,5-triazine, 2,4-diamino-6-[2-(2-ethyl-5-methylimidazol-1-yl)ethyl]-1,3,5-triazine, 2-phenyl-4,5-bis(hydroxymethyl)imidazole, and 2-phenyl-4-methyl-5-hydroxymethylimidazole.

[0092] As the imidazole-based curing accelerator whose active region does not include 130°C, a commercially available product may be used, for example, "2E4MZ", "2PZ-CN", "2PZCNS-PW", "2MZ-A", "2E4MZ-A", "2PHZ-PW", "2P4MHZ-PW", "2P4MZ", etc. manufactured by Shikoku Chemical Industry Co., Ltd.

[0093] Examples of the phosphorus-based curing accelerator include aliphatic phosphonium salts such as tetrabutylphosphonium bromide, tetrabutylphosphonium chloride, tetrabutylphosphonium acetate, tetrabutylphosphonium decanoate, tetrabutylphosphonium laurate, bis(tetrabutylphosphonium)pyromellitate, tetrabutylphosphonium hydrogenhexahydrophthalate, tetrabutylphosphonium 2,6-bis[(2-hydroxy-5-methylphenyl)methyl]-4-methylphenolate, and di-tert-butylmethylphosphonium tetraphenylborate; methyltriphenylphosphonium bromide, ethyltriphenylphosphonium bromide, propyltriphenylphosphonium bromide, butyltriphenylphosphonium bromide, benzyltriphenylphosphonium chloride, tetraphenylphosphonium bromide, p-tolyltriphenylphosphonium tetra-p-tolylborate ... aromatic phosphonium salts such as tetraphenylborate, tetraphenylphosphonium tetra-p-tolylborate, triphenylethylphosphonium tetraphenylborate, tris(3-methylphenyl)ethylphosphonium tetraphenylborate, tris(2-methoxyphenyl)ethylphosphonium tetraphenylborate, (4-methylphenyl)triphenylphosphonium thiocyanate, tetraphenylphosphonium thiocyanate, and butyltriphenylphosphonium thiocyanate; aromatic phosphine-borane complexes such as triphenylphosphine-triphenylborane; aromatic phosphine-quinone adducts such as triphenylphosphine-p-benzoquinone adduct; aliphatic phosphines such as tributylphosphine, tri-tert-butylphosphine, trioctylphosphine, di-tert-butyl(2-butenyl)phosphine, di-tert-butyl(3-methyl-2-butenyl)phosphine, and tricyclohexylphosphine;Dibutylphenylphosphine, di-tert-butylphenylphosphine, methyldiphenylphosphine, ethyldiphenylphosphine, butyldiphenylphosphine, diphenylcyclohexylphosphine, triphenylphosphine, tri-o-tolylphosphine, tri-m-tolylphosphine, tri-p-tolylphosphine, tris(4-ethylphenyl)phosphine, tris(4-propylphenyl)phosphine, tris(4-isopropylphenyl)phosphine, tris(4-butylphenyl)phosphine, tris(4-tert-butylphenyl)phosphine, tris(2,4-dimethylphenyl)phosphine, tris(2,5-dimethylphenyl)phosphine, tris(2,6-dimethylphenyl)phosphine Examples of aromatic phosphines include tris(3,5-dimethylphenyl)phosphine, tris(2,4,6-trimethylphenyl)phosphine, tris(2,6-dimethyl-4-ethoxyphenyl)phosphine, tris(2-methoxyphenyl)phosphine, tris(4-methoxyphenyl)phosphine, tris(4-ethoxyphenyl)phosphine, tris(4-tert-butoxyphenyl)phosphine, diphenyl-2-pyridylphosphine, 1,2-bis(diphenylphosphino)ethane, 1,3-bis(diphenylphosphino)propane, 1,4-bis(diphenylphosphino)butane, 1,2-bis(diphenylphosphino)acetylene, and 2,2'-bis(diphenylphosphino)diphenyl ether.

[0094] Examples of the urea-based curing accelerator include 1,1-dimethylurea; aliphatic dimethylureas such as 1,1,3-trimethylurea, 3-ethyl-1,1-dimethylurea, 3-cyclohexyl-1,1-dimethylurea, and 3-cyclooctyl-1,1-dimethylurea; 3-phenyl-1,1-dimethylurea, 3-(4-chlorophenyl)-1,1-dimethylurea, 3-(3,4-dichlorophenyl)-1,1-dimethylurea, 3-(3-chloro-4-methylphenyl)-1,1-dimethylurea, 3-(2-methylphenyl)-1,1-dimethylurea, 3-(4-methylphenyl)-1,1-dimethylurea, and 3-(3,4-dimethylphenyl)-1,1-dimethylurea. aromatic dimethylureas such as butylurea, 3-(4-isopropylphenyl)-1,1-dimethylurea, 3-(4-methoxyphenyl)-1,1-dimethylurea, 3-(4-nitrophenyl)-1,1-dimethylurea, 3-[4-(4-methoxyphenoxy)phenyl]-1,1-dimethylurea, 3-[4-(4-chlorophenoxy)phenyl]-1,1-dimethylurea, 3-[3-(trifluoromethyl)phenyl]-1,1-dimethylurea, N,N-(1,4-phenylene)bis(N',N'-dimethylurea), and N,N-(4-methyl-1,3-phenylene)bis(N',N'-dimethylurea) [toluene bisdimethylurea].

[0095] Examples of the guanidine curing accelerator include dicyandiamide, 1-methylguanidine, 1-ethylguanidine, 1-cyclohexylguanidine, 1-phenylguanidine, 1-(o-tolyl)guanidine, dimethylguanidine, diphenylguanidine, trimethylguanidine, tetramethylguanidine, pentamethylguanidine, 1,5,7-triazabicyclo[4.4.0]dec-5-ene, 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene, 1-methylbiguanide, 1-ethylbiguanide, 1-n-butylbiguanide, 1-n-octadecylbiguanide, 1,1-dimethylbiguanide, 1,1-diethylbiguanide, 1-cyclohexylbiguanide, 1-allylbiguanide, 1-phenylbiguanide, and 1-(o-tolyl)biguanide.

[0096] Examples of metal-based curing accelerators include organometallic complexes or organometallic salts of metals such as cobalt, copper, zinc, iron, nickel, manganese, and tin. Specific examples of organometallic complexes include organocobalt complexes such as cobalt(II) acetylacetonate and cobalt(III) acetylacetonate, organocopper complexes such as copper(II) acetylacetonate, organozinc complexes such as zinc(II) acetylacetonate, organoiron complexes such as iron(III) acetylacetonate, organonickel complexes such as nickel(II) acetylacetonate, and organomanganese complexes such as manganese(II) acetylacetonate. Examples of organometallic salts include zinc octylate, tin octylate, zinc naphthenate, cobalt naphthenate, tin stearate, and zinc stearate.

[0097] Examples of the amine curing accelerator include trialkylamines such as triethylamine and tributylamine, 4-dimethylaminopyridine, benzyldimethylamine, 2,4,6-tris(dimethylaminomethyl)phenol, and 1,8-diazabicyclo(5,4,0)-undecene.

[0098] As the amine-based curing accelerator, a commercially available product may be used, for example, "MY-25" manufactured by Ajinomoto Fine-Techno Co., Ltd.

[0099] The content of the (D') other curing accelerator in the resin composition may be preferably 0.08% by mass or less, more preferably 0.07% by mass or less, even more preferably 0.06% by mass or less, and particularly preferably 0.05% by mass or less, based on 100% by mass of the non-volatile components in the resin composition. The lower limit of the content is not particularly limited, but may be, for example, 0% by mass or more, 0.001% by mass or more, 0.01% by mass or more, based on 100% by mass of the non-volatile components in the resin composition.

[0100] The content of the (D') other curing accelerator in the resin composition may be preferably 0.3% by mass or less, more preferably 0.2% by mass or less, even more preferably 0.15% by mass or less, and particularly preferably 0.1% by mass or less, when the resin component in the resin composition is 100% by mass. The lower limit of the content is not particularly limited, but may be, for example, 0% by mass or more, 0.001% by mass or more, 0.01% by mass or more, etc., when the resin component in the resin composition is 100% by mass.

[0101] <(E) Stress relaxation component> The resin composition of the present invention may further contain a (E) stress relaxation component as an optional component. The (E) stress relaxation component means a resin having flexibility, and may be a particulate resin component (particulate stress relaxation component) that maintains the shape of particles in the resin composition, or a non-particulate resin component (non-particulate stress relaxation component) that tends to be mixed or dissolved in the resin composition, and only one of them or both of them may be included, and the resin components forming them may be a resin that exhibits rubber elasticity itself, or a resin that exhibits rubber elasticity by reacting with other components. Examples of resins that exhibit rubber elasticity include resins that exhibit an elastic modulus of 1 GPa or less when a tensile test is performed in accordance with the Japanese Industrial Standards (JIS K7161) at a temperature of 25°C and a humidity of 40% RH.

[0102] The particulate stress relaxation component is preferably spherical. The particulate stress relaxation component may be a hollow particle having a hole inside the particle, or a non-hollow particle having no hole inside the particle. The hollow particle may be a monohollow particle having only one hole inside the particle, or a polyhollow particle having multiple holes inside the particle.

[0103] The particulate stress relaxation component is, for example, a rubber particle containing a rubber component, and is preferably a rubber particle containing a silicone-based elastomer such as polydimethylsiloxane; an olefin-based thermoplastic elastomer such as polybutadiene, polyisoprene, polychlorobutadiene, ethylene-vinyl acetate copolymer, styrene-butadiene copolymer, styrene-isoprene copolymer, styrene-isobutylene copolymer, acrylonitrile-butadiene copolymer, isoprene-isobutylene copolymer, isobutylene-butadiene copolymer, ethylene-propylene-butadiene terpolymer, ethylene-propylene-butene terpolymer; an acrylic thermoplastic elastomer such as polypropyl (meth)acrylate, polybutyl (meth)acrylate, polycyclohexyl (meth)acrylate, polyoctyl (meth)acrylate, etc., as a rubber component. Furthermore, the rubber component may be mixed with a silicone-based rubber such as polyorganosiloxane rubber. The rubber component contained in the rubber particles has a glass transition temperature of, for example, 0° C. or lower, preferably −10° C. or lower, more preferably −20° C. or lower, and even more preferably −30° C. or lower.

[0104] From the viewpoint of obtaining the desired effect of the present invention remarkably, the particulate stress relaxation component preferably contains core-shell type rubber particles. The core-shell type rubber particles are particulate stress relaxation components consisting of a core particle containing a rubber component as described above and one or more shell layers covering the core particle. Furthermore, the core-shell type rubber particles are preferably core-shell type graft copolymer rubber particles consisting of a core particle containing a rubber component as described above and a shell portion obtained by graft copolymerization of a monomer component copolymerizable with the rubber component contained in the core particle. The core-shell type here does not necessarily refer only to those in which the core particle and the shell portion are clearly distinguishable, but also includes those in which the boundary between the core particle and the shell portion is unclear, and the core particle does not necessarily have to be completely covered with the shell portion.

[0105] The rubber component is preferably contained in the core-shell rubber particles in an amount of 40% by mass or more, more preferably 50% by mass or more, and even more preferably 60% by mass or more. The upper limit of the rubber component content in the core-shell rubber particles is not particularly limited, but is preferably, for example, 95% by mass or less, and more preferably 90% by mass, from the viewpoint of sufficiently covering the core particles with the shell portion.

[0106] The monomer components forming the shell of the core-shell type rubber particles include, for example, (meth)acrylic acid esters such as methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, cyclohexyl (meth)acrylate, octyl (meth)acrylate, and glycidyl (meth)acrylate; (meth)acrylic acid; N-substituted maleimides such as N-methylmaleimide and N-phenylmaleimide; maleimide; α,β-unsaturated carboxylic acids such as maleic acid and itaconic acid; aromatic vinyl compounds such as styrene, 4-vinyltoluene, and α-methylstyrene; (meth)acrylonitrile, and among them, it is preferable to include (meth)acrylic acid esters, and more preferably to include methyl (meth)acrylate. Note that "(meth)acrylic acid" refers to methacrylic acid or acrylic acid.

[0107] Commercially available core-shell type rubber particles include, for example, "CHT" manufactured by Samsung SDI; "B602" manufactured by Techno UMG; "Paraloid EXL-2602", "Paraloid EXL-2603", "Paraloid EXL-2655", "Paraloid EXL-2311", "Paraloid-EXL2313", "Paraloid EXL-2315", "Paraloid KM-330", "Paraloid KM-336P", and "Paraloid KM-336P" manufactured by Dow Chemical Japan. Examples of such materials include "Laroid KCZ-201" manufactured by Mitsubishi Rayon Co., Ltd., "Metabrene C-223A", "Metabrene E-901", "Metabrene S-2001", "Metabrene W-450A", and "Metabrene SRK-200" manufactured by Kaneka Corporation, "Kane Ace M-511", "Kane Ace M-600", "Kane Ace M-400", "Kane Ace M-580", and "Kane Ace MR-01" manufactured by Kanz Chemical Co., Ltd., and "AC3401N" and "AC3816N" manufactured by Ganz Chemical Co., Ltd.

[0108] The average particle size (average primary particle size) of the particulate stress relaxation component is not particularly limited, but is preferably 20 nm or more, more preferably 30 nm or more, and even more preferably 50 nm or more. The upper limit of the average particle size (average primary particle size) of the particulate stress relaxation component is not particularly limited, but is preferably 10,000 nm or less, more preferably 5,000 nm or less, and even more preferably 1,000 nm or less. The average particle size (average primary particle size) of the particulate stress relaxation component can be measured using a zeta potential particle size distribution measuring device or the like.

[0109] The non-particulate stress relaxation component preferably contains a resin having one or more structures selected from polybutadiene structure, polysiloxane structure, poly(meth)acrylate structure, polyalkylene structure, polyalkyleneoxy structure, polyisoprene structure, polyisobutylene structure, and polycarbonate structure in the molecule, more preferably contains a resin having one or more structures selected from polybutadiene structure and polycarbonate structure, and particularly preferably contains a resin having a polybutadiene structure and a phenolic hydroxyl group (phenolic hydroxyl group-containing polybutadiene resin) or a resin having a polycarbonate structure (polycarbonate resin). Note that "(meth)acrylate" refers to methacrylate and acrylate.

[0110] The polybutadiene structure includes not only a structure formed by polymerizing butadiene, but also a structure formed by hydrogenating the structure. The polybutadiene structure may be partially or entirely hydrogenated. Furthermore, the polybutadiene structure may be included in the main chain or in the side chain of the stress relaxation component molecule.

[0111] Preferred examples of polybutadiene resins include hydrogenated polybutadiene skeleton-containing resins, hydroxyl group-containing polybutadiene resins, phenolic hydroxyl group-containing polybutadiene resins, carboxyl group-containing polybutadiene resins, acid anhydride group-containing polybutadiene resins, epoxy group-containing polybutadiene resins, isocyanate group-containing polybutadiene resins, and urethane group-containing polybutadiene resins. Among them, phenolic hydroxyl group-containing polybutadiene resins and epoxy group-containing polybutadiene resins are more preferred, and phenolic hydroxyl group-containing polybutadiene resins are particularly preferred. Here, "hydrogenated polybutadiene skeleton-containing resins" refers to resins in which at least a part of the polybutadiene skeleton is hydrogenated, and it is not necessarily a resin in which the polybutadiene skeleton is completely hydrogenated. Examples of hydrogenated polybutadiene skeleton-containing resins include hydrogenated polybutadiene skeleton-containing epoxy resins. Examples of preferred phenolic hydroxyl group-containing polybutadiene resins include those made from hydroxyl group-terminated polybutadiene, diisocyanate compounds, and phenolic hydroxyl group-containing resins. Here, the hydroxyl group-terminated polybutadiene and diisocyanate compounds are the same as those exemplified below. Examples of phenolic hydroxyl group-containing resins include cresol novolac resins.

[0112] Specific examples of polybutadiene resins include "PB-3600" (epoxy group-containing polybutadiene) manufactured by Daicel Corporation, "JP-100" and "JP-200" (epoxy group-containing polybutadiene) manufactured by Nippon Soda Co., Ltd., "Ricon 657" (epoxy group-containing polybutadiene), "Ricon 130MA8", "Ricon 130MA13", "Ricon 130MA20", "Ricon 131MA5", "Ricon 131MA10", "Ricon 131MA17", "Ricon 131MA20", and "Ricon Examples of such compounds include "184MA6" (polybutadiene containing an acid anhydride group), "GQ-1000" (polybutadiene with hydroxyl and carboxyl groups introduced), "G-1000", "G-2000", and "G-3000" (polybutadiene with hydroxyl groups at both ends), "GI-1000", "GI-2000", and "GI-3000" (polybutadiene with hydrogenated hydroxyl groups at both ends) manufactured by Nippon Soda Co., Ltd., "PB3600" and "PB4700" (polybutadiene skeleton epoxy compound), "Epofriend A1005", "Epofriend A1010", and "Epofriend A1020" (epoxy compound of styrene, butadiene, and styrene block copolymer) manufactured by Daicel Corporation, and "FCA-061L" (hydrogenated polybutadiene skeleton epoxy compound) and "R-45EPT" (polybutadiene skeleton epoxy compound) manufactured by Nagase ChemteX Corporation.

[0113] In addition, examples of preferred polybutadiene resins include linear polyimides (polyimides described in JP 2006-37083 A and WO 2008 / 153208 A) made from hydroxyl-terminated polybutadiene, diisocyanate compounds, and polybasic acids or their anhydrides. The content of the polybutadiene structure in the polyimide resin is preferably 60% by mass to 95% by mass, more preferably 75% by mass to 85% by mass. For details of the polyimide resin, refer to the descriptions in JP 2006-37083 A and WO 2008 / 153208 A, the contents of which are incorporated herein by reference.

[0114] The number average molecular weight of the hydroxyl-terminated polybutadiene is preferably 500 to 5,000, more preferably 800 to 3,500. The hydroxyl equivalent of the hydroxyl-terminated polybutadiene is preferably 250 to 5,000 g / eq., more preferably 1,000 to 3,000 g / eq.

[0115] Examples of the diisocyanate compound include aromatic diisocyanates such as toluene-2,4-diisocyanate, toluene-2,6-diisocyanate, xylylene diisocyanate, diphenylmethane diisocyanate, etc., aliphatic diisocyanates such as hexamethylene diisocyanate, etc., and alicyclic diisocyanates such as isophorone diisocyanate, etc. Among these, aromatic diisocyanates are preferred, and toluene-2,4-diisocyanate is more preferred.

[0116] Examples of polybasic acids or anhydrides thereof include tetrabasic acids and anhydrides thereof, such as ethylene glycol bistrimellitic acid, pyromellitic acid, benzophenone tetracarboxylic acid, biphenyl tetracarboxylic acid, naphthalene tetracarboxylic acid, 5-(2,5-dioxotetrahydrofuryl)-3-methyl-cyclohexene-1,2-dicarboxylic acid, and 3,3'-4,4'-diphenylsulfone tetracarboxylic acid; tribasic acids and anhydrides thereof, such as trimellitic acid and cyclohexane tricarboxylic acid; and 1,3,3a,4,5,9b-hexahydro-5-(tetrahydro-2,5-dioxo-3-furanyl)-naphtho(1,2-C)furan-1,3-dione.

[0117] The polybutadiene resin may also contain a polystyrene structure that has a structure obtained by polymerizing styrene.

[0118] Specific examples of polystyrene resins, which are resins having a polystyrene structure in their molecules, include styrene-butadiene-styrene block copolymers (SBS), styrene-isoprene-styrene block copolymers (SIS), styrene-ethylene-butylene-styrene block copolymers (SEBS), styrene-ethylene-propylene-styrene block copolymers (SEPS), styrene-ethylene-ethylene-propylene-styrene block copolymers (SEEPS), styrene-butadiene-butylene-styrene block copolymers (SBBS), styrene-butadiene diblock copolymers, hydrogenated styrene-butadiene block copolymers, hydrogenated styrene-isoprene block copolymers, and hydrogenated styrene-butadiene random copolymers.

[0119] The polystyrene resin may be a commercially available product, for example, hydrogenated styrene-based thermoplastic elastomer "H1041", "Tuftec H1043", "Tuftec P2000", "Tuftec MP10" (manufactured by Asahi Kasei Corporation); epoxidized styrene-butadiene thermoplastic elastomer "Epofriend AT501", "CT310" (manufactured by Daicel Corporation); modified styrene-based elastomer having a hydroxyl group "Septon HG252" (manufactured by Kuraray Co., Ltd.); modified styrene-based elastomer having a carboxyl group "Tuftec N503M", modified styrene-based elastomer having an amino group "Tuftec N501", modified styrene-based elastomer having an acid anhydride group "Tuftec M1913" (manufactured by Asahi Kasei Corporation); unmodified styrene-based elastomer "Septon S8104" (manufactured by Kuraray Co., Ltd.). The (E) stress relaxation component may be used alone or in combination of two or more types.

[0120] The polysiloxane structure is a structure containing a siloxane bond, and is contained in, for example, silicone rubber. The polysiloxane structure may be contained in the main chain or in the side chain of the stress relaxation component molecule.

[0121] Specific examples of polysiloxane resins, which are resins having a polysiloxane structure in the molecule, include "SMP-2006," "SMP-2003PGMEA," and "SMP-5005PGMEA" manufactured by Shin-Etsu Silicones Co., Ltd., amine-terminated polysiloxanes, and linear polyimides made from tetrabasic acid anhydrides (WO 2010 / 053185).

[0122] The poly(meth)acrylate structure is a structure formed by polymerizing acrylic acid or an acrylic acid ester, and also includes a structure formed by polymerizing methacrylic acid or a methacrylic acid ester. The (meth)acrylate structure may be contained in the main chain or in the side chain of the stress relaxation component molecule.

[0123] Preferred examples of poly(meth)acrylate resins, which are resins having a poly(meth)acrylate structure in the molecule, include hydroxy group-containing poly(meth)acrylate resins, phenolic hydroxy group-containing poly(meth)acrylate resins, carboxy group-containing poly(meth)acrylate resins, acid anhydride group-containing poly(meth)acrylate resins, epoxy group-containing poly(meth)acrylate resins, isocyanate group-containing poly(meth)acrylate resins, and urethane group-containing poly(meth)acrylate resins.

[0124] Specific examples of poly(meth)acrylate resins include Nagase Chemtex Corporation's Teisan Resin "SG-70L", "SG-708-6", "WS-023", "SG-700AS", and "SG-280TEA" (carboxy group-containing acrylic acid ester copolymer resin, acid value 5 to 34 mgKOH / g, weight average molecular weight 400,000 to 900,000, Tg -30 ° C to 5 ° C), "SG-80H", "SG-80H-3", and "SG-P3" (epoxy group-containing acrylic acid ester copolymer resin, epoxy equivalent 4761 to 14285 g / eq, weight average molecular weight 350,000). ~850,000, Tg 11°C~12°C), "SG-600TEA", "SG-790" (hydroxy group-containing acrylic ester copolymer resin, hydroxyl value 20~40mgKOH / g, weight average molecular weight 500,000~1.2 million, Tg -37°C~-32°C), Negami Chemical Industries' "ME-2000", "W-116.3" (carboxy group-containing acrylic ester copolymer resin), "W-197C" (hydroxy group-containing acrylic ester copolymer resin), "KG-25", "KG-3000" (epoxy group-containing acrylic ester copolymer resin), etc.

[0125] The polyalkylene structure preferably has a predetermined number of carbon atoms. The specific number of carbon atoms in the polyalkylene structure is preferably 2 or more, more preferably 3 or more, particularly preferably 5 or more, and preferably 15 or less, more preferably 10 or less, particularly preferably 6 or less. The polyalkylene structure may be contained in the main chain or in the side chain of the stress relaxation component molecule.

[0126] The polyalkyleneoxy structure preferably has a predetermined number of carbon atoms. The specific number of carbon atoms in the polyalkyleneoxy structure is preferably 2 or more, preferably 3 or more, more preferably 5 or more, and preferably 15 or less, more preferably 10 or less, particularly preferably 6 or less. The polyalkyleneoxy structure may be contained in the main chain or in the side chain of the stress relaxation component molecule.

[0127] Specific examples of polyalkylene resins, which are resins having a polyalkylene structure in the molecule, and polyalkyleneoxy resins, which are resins having a polyalkyleneoxy structure in the molecule, include "PTXG-1000" and "PTXG-1800" manufactured by Asahi Kasei Fibers Corporation, "YX-7180" (a resin containing an alkylene structure having an ether bond) manufactured by Mitsubishi Chemical Corporation, "EXA-4850-150", "EXA-4816", and "EXA-4822" manufactured by DIC Corporation, "EP-4000", "EP-4003", "EP-4010", and "EP-4011" manufactured by ADEKA Corporation, "BEO-60E" and "BPO-20E" manufactured by New Japan Chemical Co., Ltd., and "YL7175" and "YL7410" manufactured by Mitsubishi Chemical Corporation.

[0128] The polyisoprene structure may be contained in the main chain or in the side chain of the stress relaxation component molecule. Specific examples of polyisoprene resins that have a polyisoprene structure in the molecule include "KL-610" and "KL-613" manufactured by Kuraray Co., Ltd.

[0129] The polyisobutylene structure may be contained in the main chain or in the side chain of the stress relaxation component molecule. Specific examples of polyisobutylene resins that have a polyisobutylene structure in the molecule include "SIBSTAR-073T" (styrene-isobutylene-styrene triblock copolymer) and "SIBSTAR-042D" (styrene-isobutylene diblock copolymer) manufactured by Kaneka Corporation.

[0130] The polycarbonate structure may be contained in the main chain or in a side chain of the stress relaxation component molecule.

[0131] Preferred examples of the polycarbonate resin, which is a resin having a polycarbonate structure in the molecule, include a hydroxy group-containing polycarbonate resin, a phenolic hydroxy group-containing polycarbonate resin, a carboxy group-containing polycarbonate resin, an acid anhydride group-containing polycarbonate resin, an epoxy group-containing polycarbonate resin, an isocyanate group-containing polycarbonate resin, and a urethane group-containing polycarbonate resin.

[0132] Specific examples of polycarbonate resins include "T6002" and "T6001" (polycarbonate diols) manufactured by Asahi Kasei Corporation, and "C-1090", "C-2090", and "C-3090" (polycarbonate diols) manufactured by Kuraray Co., Ltd.

[0133] In addition, examples of preferred polycarbonate resins include linear polyimides made from hydroxyl-terminated polycarbonates, diisocyanate compounds, and polybasic acids or their anhydrides. The linear polyimides have a urethane structure and a polycarbonate structure. The content of the polycarbonate structure in the polyimide resin is preferably 60% by mass to 95% by mass, more preferably 75% by mass to 85% by mass. For details of the polyimide resin, refer to the description in International Publication No. 2016 / 129541, the contents of which are incorporated herein by reference.

[0134] The number average molecular weight of the hydroxyl group-terminated polycarbonate is preferably 500 to 5,000, and more preferably 1,000 to 3,000. The hydroxyl group equivalent of the hydroxyl group-terminated polycarbonate is preferably 250 to 1,250.

[0135] The non-particulate stress relaxation component preferably further has an imide structure, which can enhance the heat resistance of the non-particulate stress relaxation component and effectively enhance the crack resistance.

[0136] The non-particulate stress relaxation component may have any of a linear, branched, or cyclic structure, but is preferably linear.

[0137] The non-particulate stress relaxation component preferably further has a functional group capable of reacting with the epoxy resin. This functional group includes a reactive group that appears upon heating. By having the non-particulate stress relaxation component have a functional group, the mechanical strength of the cured product of the resin composition can be improved.

[0138] Examples of the functional group include a carboxy group, a hydroxy group, an acid anhydride group, a phenolic hydroxyl group, an epoxy group, an isocyanate group, and a urethane group. Among them, from the viewpoint of obtaining the effects of the present invention remarkably, the functional group preferably has one or more functional groups selected from a hydroxyl group, an acid anhydride group, a phenolic hydroxyl group, an epoxy group, an isocyanate group, and a urethane group, and a phenolic hydroxyl group is particularly preferable.

[0139] The non-particulate stress relaxation component may be used alone or in combination of two or more kinds.

[0140] The specific number average molecular weight Mn of the non-particulate stress relaxation component is preferably 500 or more, more preferably 800 or more, even more preferably 1,000 or more, particularly preferably 1,200 or more, and is preferably 100,000 or less, more preferably 50,000 or less, particularly preferably 10,000 or less. The number average molecular weight Mn of the non-particulate stress relaxation component is a polystyrene-equivalent number average molecular weight measured using GPC (gel permeation chromatography).

[0141] When the non-particulate stress relaxation component has a functional group, the functional group equivalent of the non-particulate stress relaxation component is preferably 100 g / eq. or more, more preferably 200 g / eq. or more, even more preferably 1,000 g / eq. or more, particularly preferably 2,500 g / eq. or more, and preferably 50,000 g / eq. or less, more preferably 30,000 g / eq. or less, even more preferably 10,000 g / eq. or less, particularly preferably 5,000 g / eq. or less. The functional group equivalent is the number of grams of a resin containing 1 gram equivalent of a functional group. For example, the epoxy group equivalent can be measured according to JIS K7236. Also, for example, the hydroxyl group equivalent can be calculated by dividing the molecular weight of KOH by the hydroxyl value measured according to JIS K1557-1.

[0142] The glass transition temperature (Tg) of the (E) stress relaxation component is preferably 20° C. or lower, more preferably 10° C. or lower, and even more preferably 0° C. or lower.

[0143] The content of the (E) stress relaxation component in the resin composition may be preferably 3% by mass or less, more preferably 2% by mass or less, further preferably 1.5% by mass or less, and particularly preferably 1.2% by mass or less, based on 100% by mass of the nonvolatile components in the resin composition. The lower limit of the content may be 0% by mass or more, 0.001% by mass or more, 0.01% by mass or more, based on 100% by mass of the nonvolatile components in the resin composition.

[0144] The content of the (E) stress relaxation component in the resin composition may be preferably 4% by mass or less, more preferably 3.8% by mass or less, even more preferably 3.5% by mass or less, and particularly preferably 3% by mass or less, when the resin components in the resin composition are taken as 100% by mass. The lower limit of the content of the (E) stress relaxation component in the resin composition may be 0% by mass or more, 0.001% by mass or more, 0.01% by mass, etc., when the resin components in the resin composition are taken as 100% by mass.

[0145] <(F) Dimer acid skeleton-containing components> The resin composition may further contain, as an optional component, (F) a dimer acid skeleton-containing component. The dimer acid skeleton-containing component is preferably a maleimide resin having a carbon skeleton derived from a dimer acid.

[0146] The carbon skeleton derived from dimer acid means a carbon skeleton obtained by removing two terminal carboxyl groups (-COOH) of dimer acid, or a carbon skeleton obtained by replacing two terminal carboxyl groups (-COOH) with methylene groups (-CH2-). Dimer acid is a known compound obtained by dimerizing unsaturated fatty acids (preferably those having 11 to 22 carbon atoms, more preferably those having 14 to 20 carbon atoms, and particularly preferably those having 18 carbon atoms), and its industrial production process is almost standardized in the industry. Dimer acid is easily obtained, and is mainly composed of dimer acid having 36 carbon atoms obtained by dimerizing unsaturated fatty acids having 18 carbon atoms, such as oleic acid and linoleic acid, which are particularly inexpensive and easily available. In addition, dimer acid may contain any amount of monomer acid, trimer acid, other polymerized fatty acid, etc., depending on the production method, degree of purification, etc. In addition, although double bonds remain after the polymerization reaction of unsaturated fatty acids, in this specification, hydrogenated products in which the degree of unsaturation is reduced by further hydrogenation reaction are also included in dimer acid.

[0147] Maleimide resins having a carbon skeleton derived from dimer acid are represented by the formula (3):

[0148] [ka]

[0149] [In the formula, n+1 X's each independently represent a divalent organic group consisting of five or more skeletal atoms selected from carbon atoms, nitrogen atoms (not forming an imide), oxygen atoms, and sulfur atoms, and non-skeletal atoms selected from hydrogen atoms and halogen atoms, and at least one of the n+1 X's represents a divalent hydrocarbon group derived from a dimer acid; n Y's each independently represent a tetravalent organic group having five or more skeletal atoms selected from carbon atoms, nitrogen atoms (not forming an imide), oxygen atoms, and sulfur atoms, and non-skeletal atoms selected from hydrogen atoms and halogen atoms; n represents an integer of 0 or 1 or more. It is preferable that the maleimide resin contains a maleimide resin represented by the following formula:

[0150] The n+1 Xs each independently represent a divalent organic group consisting of 5 or more (preferably 5 to 200, more preferably 5 to 100, and even more preferably 5 to 50) skeletal atoms selected from carbon atoms, nitrogen atoms (not forming an imide), oxygen atoms, and sulfur atoms, and non-skeletal atoms selected from hydrogen atoms and halogen atoms, and at least one of the n+1 Xs represents a divalent hydrocarbon group derived from a dimer acid.

[0151] The halogen atom is a fluorine atom, a chlorine atom, a bromine atom, or an iodine atom.

[0152] The divalent hydrocarbon group derived from a dimer acid means a divalent hydrocarbon group obtained by removing the two terminal carboxy groups (-COOH) of a dimer acid, or a divalent hydrocarbon group obtained by replacing the two terminal carboxy groups (-COOH) with a methylene group (-CH-).

[0153] The n+1 X's may have a divalent organic group other than a divalent hydrocarbon group derived from a dimer acid, but when the n+1 X's are taken as 100 mol%, it is preferable that 30 mol% or more of them are divalent hydrocarbon groups derived from a dimer acid, more preferably 60 mol% or more of them are divalent hydrocarbon groups derived from a dimer acid, even more preferably 90 mol% or more of them are divalent hydrocarbon groups derived from a dimer acid, and it is particularly preferable that (all) the n+1 X's are divalent hydrocarbon groups derived from a dimer acid.

[0154] The divalent organic group other than the divalent hydrocarbon group derived from a dimer acid may be a divalent organic group that does not have an aromatic ring, or may be a divalent organic group that has an aromatic ring.

[0155] The n Ys each independently represent a tetravalent organic group consisting of 5 or more (preferably 5 to 200, more preferably 5 to 100, and even more preferably 5 to 50) skeletal atoms selected from carbon atoms, nitrogen atoms (not forming imides), oxygen atoms, and sulfur atoms, and non-skeletal atoms selected from hydrogen atoms and halogen atoms. The tetravalent organic group represented by Y may be a tetravalent organic group having no aromatic ring, or may be a tetravalent organic group having an aromatic ring.

[0156] In one embodiment, the tetravalent organic group represented by Y is preferably represented by any one of the formulae (Y1) to (Y5):

[0157] [ka]

[0158] [In the formula, Ring Y 11 , ring Y 21 , ring Y 22 , ring Y 31 , ring Y 32 , ring Y 33 , ring Y 41 , ring Y 42 , ring Y 43 , ring Y 44 , ring Y 51 , ring Y 52 , ring Y 53 , ring Y 54 and ring Y 55 each independently represents an aromatic ring which may have a substituent, or a non-aromatic ring which may have a substituent; Y 2a , Y 3a , Y 3b , Y 4a , Y 4b , Y 4c , Y 5a , Y 5b , Y 5c and Y 5d are each independently a single bond, -C(R y )2-, -O-, -CO-, -S-, -SO-, -SO2-, -CONH-, or -NHCO-; R y each independently represents a hydrogen atom or an alkyl group which may be substituted with a halogen atom, or two R y are linked together to form a non-aromatic ring which may have a substituent; * indicates binding site.] The two bonding sites on the same ring represented by * are bonding sites to two adjacent carbon atoms on the ring.

[0159] Ring Y 11 , ring Y 21 , ring Y 22 , ring Y 31 , ring Y 32 , ring Y 33 , ring Y 41 , ring Y 42 , ring Y 43 , ring Y 44 , ring Y 51 , ring Y 52 , ring Y 53 , ring Y 54 and ring Y 55 each independently represents an aromatic ring which may have a substituent, or a non-aromatic ring which may have a substituent; in one embodiment, it is preferably an aromatic ring which may have a substituent, more preferably a benzene ring which may have a substituent, and even more preferably a benzene ring which may be substituted with an alkyl group.

[0160] The aromatic ring means a ring that follows the Huckel rule, in which the number of electrons contained in the π electron system on the ring is 4p+2 (p is a natural number). The aromatic ring may be an aromatic carbocycle having only carbon atoms as ring-constituting atoms, or an aromatic heterocycle having heteroatoms such as oxygen atoms, nitrogen atoms, and sulfur atoms in addition to carbon atoms as ring-constituting atoms. In one embodiment, the aromatic ring is preferably an aromatic carbocycle. In one embodiment, the aromatic ring is preferably a 5- to 14-membered aromatic ring, more preferably a 6- to 14-membered aromatic ring, and even more preferably a 6- to 10-membered aromatic ring. Suitable specific examples of the aromatic ring include a benzene ring, a naphthalene ring, an anthracene ring, and a phenanthrene ring, and more preferably a benzene ring or a naphthalene ring, and particularly preferably a benzene ring.

[0161] The non-aromatic ring means a ring other than an aromatic ring having aromaticity in the entire ring. The non-aromatic ring may be a non-aromatic carbocycle having only carbon atoms as ring-constituting atoms, or a non-aromatic heterocycle having heteroatoms such as oxygen atoms, nitrogen atoms, and sulfur atoms as ring-constituting atoms in addition to carbon atoms. In one embodiment, the non-aromatic ring is preferably a non-aromatic carbocycle. The non-aromatic ring may be a saturated ring or an unsaturated ring. The non-aromatic ring is preferably a 3- to 21-membered non-aromatic ring, more preferably a 4- to 17-membered non-aromatic ring, and even more preferably a 5- to 14-membered non-aromatic ring. Specific preferred examples of the non-aromatic ring include monocyclic non-aromatic saturated carbon rings such as a cyclobutane ring, a cyclopentane ring, a cyclohexane ring, a cycloheptane ring, and a cyclooctane ring; monocyclic non-aromatic unsaturated carbon rings such as a cyclobutene ring, a cyclopentene ring, a cyclohexene ring, a cycloheptene ring, a cyclooctene ring, a cyclopentadiene ring, and a cyclohexadiene ring; bicyclo[2.2.1]heptane ring (norbornane ring), bicyclo[4.4.0]decane ring (decalin ring), bicyclo[5.3.0]decane ring, bicyclo[4.3.0]nonane ring (hydrindane ring), bicyclo[3.2.1]octane ring, bicyclo[5.4.0]undecane ring, bicyclo[3.3.0]octane ring, bicyclo[3.3.1]nonane ring, tricyclo[5.2.1.0 2,6 ] Decane ring (tetrahydrodicyclopentadiene ring), tricyclo[3.3.1.1 3,7]Decane ring (adamantane ring), tricyclo[6.2.1.0 2,7 ] undecane ring and other bicyclic or higher non-aromatic saturated carbocyclic rings; bicyclo[2.2.1] hept-2-ene ring (norbornene ring), bicyclo[2.2.2] oct-2-ene ring, bicyclo[4.4.0] dec-2-ene ring and other bicyclic or higher non-aromatic unsaturated carbocyclic rings. The non-aromatic ring may be a non-aromatic ring partially condensed with an aromatic ring. Examples of the non-aromatic ring partially condensed with an aromatic ring include an indane ring, an indene ring, a tetralin ring, a 1,2-dihydronaphthalene ring, a 1,4-dihydronaphthalene ring, a fluorene ring, a 9,10-dihydroanthracene ring, and a 9,10-dihydrophenanthrene ring.

[0162] Ring Y 11 , ring Y 21 , ring Y 22 , ring Y 31 , ring Y 32 , ring Y 33 , ring Y 41 , ring Y 42 , ring Y 43 , ring Y 44 , ring Y 51 , ring Y 52 , ring Y 53 , ring Y 54 and ring Y 55 The "substituent" in the "optionally substituted aromatic ring" and the "optionally substituted non-aromatic ring" is not particularly limited, and examples thereof include monovalent substituents such as halogen atoms, -NO2, -CN, -COH, -OH, -SH, -NH2, -COOH, -R, -COR, -OR, -SR, -SOR, -SOR, -NHR, -N(R)2, -COOR, -OCOR, -CONH2, -CONHR, -CON(R)2, and -NHCOR (wherein each R is independently a monovalent hydrocarbon group).

[0163] A monovalent hydrocarbon group is a monovalent hydrocarbon group having one or more (preferably 1 to 50, more preferably 1 to 20) carbon atoms as skeletal atoms and hydrogen atoms as non-skeletal atoms. The monovalent hydrocarbon group may be a monovalent saturated hydrocarbon group or a monovalent unsaturated hydrocarbon group. The monovalent hydrocarbon group may or may not have an aromatic structure. Examples of the monovalent hydrocarbon group include an alkyl group, an alkenyl group, an aryl group, an aralkyl group, and an alkylaryl group.

[0164] Y 2a , Y 3a , Y 3b , Y 4a , Y 4b , Y 4c , Y 5a , Y 5b , Y 5c and Y 5d are each independently a single bond, -C(R y )2-, -O-, -CO-, -S-, -SO-, -SO2-, -CONH-, or -NHCO-; in one embodiment, preferably a single bond, -C(R y )2-, or -O-.

[0165] R y each independently represents a hydrogen atom or an alkyl group which may be substituted with a halogen atom, or two R y are bonded together to form a non-aromatic ring which may have a substituent; in one embodiment, they are preferably a hydrogen atom or an alkyl group which may be substituted with a halogen atom, more preferably a hydrogen atom or a methyl group which may be substituted with a halogen atom, even more preferably a hydrogen atom, a methyl group, or a trifluoromethyl group, and particularly preferably a hydrogen atom or a methyl group.

[0166] R y The "substituent" in the "non-aromatic ring optionally having a substituent" formed by the ring Y 11The substituents are the same as those in the "optionally substituted aromatic ring" and the "optionally substituted non-aromatic ring".

[0167] n represents an integer of 0 or 1 or more; in one embodiment, n is preferably 0.

[0168] Commercially available maleimide resins having a carbon skeleton derived from a dimer acid include, for example, “BMI-689”, “BMI-1500”, “BMI-1700”, and “BMI-3000J” manufactured by Designer Molecules, and “SLK-6895-T90” manufactured by Shin-Etsu Chemical Co., Ltd.

[0169] The content of the dimer acid skeleton-containing component (F) in the resin composition may be preferably 3% by mass or less, more preferably 2% by mass or less, further preferably 1.5% by mass or less, and particularly preferably 1.2% by mass or less, based on 100% by mass of the nonvolatile components in the resin composition. The lower limit of the content may be 0% by mass or more, 0.001% by mass or more, 0.01% by mass or more, based on 100% by mass of the nonvolatile components in the resin composition.

[0170] The content of the dimer acid skeleton-containing component (F) in the resin composition may be preferably 4% by mass or less, more preferably 3.5% by mass or less, further preferably 3.2% by mass or less, and particularly preferably 3% by mass or less, based on 100% by mass of the resin components in the resin composition. The lower limit of the content may be 0% by mass or more, 0.001% by mass or more, 0.01% by mass or more, based on 100% by mass of the resin components in the resin composition.

[0171] <(G)Thermoplastic resin> The resin composition of the present invention may further contain a thermoplastic resin (G) as an optional component. The thermoplastic resin (G) is a component other than the epoxy resin (A) explained above.

[0172] Examples of the (G) thermoplastic resin include polyimide resin, phenoxy resin, polyvinyl acetal resin, polyolefin resin, polyamideimide resin, polyetherimide resin, polysulfone resin, polyethersulfone resin, polyphenylene ether resin, polyetheretherketone resin, polyester resin, etc. In one embodiment, the (G) thermoplastic resin preferably contains a thermoplastic resin selected from the group consisting of polyimide resin and phenoxy resin, and more preferably contains a phenoxy resin. The thermoplastic resin may be used alone or in combination of two or more kinds.

[0173] Specific examples of polyimide resins include "SLK-6100" manufactured by Shin-Etsu Chemical Co., Ltd., and "Rikacoat SN20" and "Rikacoat PN20" manufactured by New Japan Chemical Co., Ltd.

[0174] Examples of the phenoxy resin include phenoxy resins having one or more skeletons selected from the group consisting of bisphenol A skeleton, bisphenol F skeleton, bisphenol S skeleton, bisphenolacetophenone skeleton, novolac skeleton, biphenyl skeleton, fluorene skeleton, dicyclopentadiene skeleton, norbornene skeleton, naphthalene skeleton, anthracene skeleton, adamantane skeleton, terpene skeleton, and trimethylcyclohexane skeleton. The terminal of the phenoxy resin may be any functional group such as a phenolic hydroxyl group or an epoxy group.

[0175] Specific examples of phenoxy resins include "1256" and "4250" manufactured by Mitsubishi Chemical Corporation (both of which are phenoxy resins containing a bisphenol A skeleton); "YX8100" manufactured by Mitsubishi Chemical Corporation (phenoxy resin containing a bisphenol S skeleton); "YX6954" manufactured by Mitsubishi Chemical Corporation (phenoxy resin containing a bisphenol acetophenone skeleton), "FX280" and "FX293" manufactured by Nippon Steel Chemical & Material Co., Ltd.; and "YX7200B35", "YL7500BH30", "YX6954BH30", "YX7553BH30", "YL7769BH30", "YL6794", "YL7213", "YL7290", and "YL7482" manufactured by Mitsubishi Chemical Corporation.

[0176] Examples of polyvinyl acetal resins include polyvinyl formal resins and polyvinyl butyral resins, and polyvinyl butyral resins are preferred. Specific examples of polyvinyl acetal resins include S-LEC BH series, BX series (e.g., BX-5Z), KS series (e.g., KS-1), BL series, and BM series manufactured by Sekisui Chemical Co., Ltd.

[0177] Examples of polyolefin resins include ethylene-based copolymer resins such as low-density polyethylene, very low-density polyethylene, high-density polyethylene, ethylene-vinyl acetate copolymer, ethylene-ethyl acrylate copolymer, and ethylene-methyl acrylate copolymer; and polyolefin polymers such as polypropylene and ethylene-propylene block copolymer.

[0178] Specific examples of polyamide-imide resins include "Viromax HR11NN" and "Viromax HR16NN" manufactured by Toyobo Co., Ltd. Specific examples of polyamide-imide resins also include modified polyamide-imides such as "KS9100" and "KS9300" (polysiloxane skeleton-containing polyamide-imide) manufactured by Resonac Corporation.

[0179] A specific example of the polyethersulfone resin is "PES5003P" manufactured by Sumitomo Chemical Co., Ltd.

[0180] Specific examples of polysulfone resins include polysulfones "P1700" and "P3500" manufactured by Solvay Advanced Polymers.

[0181] A specific example of the polyphenylene ether resin is NORYL SA90 manufactured by SABIC Corp. A specific example of the polyetherimide resin is ULTEM manufactured by GE Corp.

[0182] Examples of the polyester resin include polyethylene terephthalate resin, polyethylene naphthalate resin, polybutylene terephthalate resin, polybutylene naphthalate resin, polytrimethylene terephthalate resin, polytrimethylene naphthalate resin, and polycyclohexane dimethyl terephthalate resin.

[0183] From the viewpoint of further improving film formability, the weight average molecular weight (Mw) of the (G) thermoplastic resin is preferably 5,000 or more, more preferably 8,000 or more, even more preferably 10,000 or more, particularly preferably 20,000 or more, and is preferably 100,000 or less, more preferably 70,000 or less, even more preferably 60,000 or less, particularly preferably 50,000 or less.

[0184] The content of the (G) thermoplastic resin relative to the total non-volatile components in the resin composition is not particularly limited, but when the non-volatile components in the resin composition are taken as 100 mass%, it may be preferably 3 mass% or less, more preferably 2.5 mass% or less, even more preferably 2 mass% or less, even more preferably 1.5 mass% or less, and particularly preferably 1.2 mass% or less. The lower limit of the content is not particularly limited, but when the non-volatile components in the resin composition are taken as 100 mass%, it may be, for example, 0 mass% or more, 0.01 mass% or more, 0.1 mass% or more, etc., preferably 0.5 mass% or more, more preferably 1 mass% or more.

[0185] The content of the (G) thermoplastic resin relative to the resin components in the resin composition is not particularly limited, but when the resin components in the resin composition are taken as 100 mass%, it may be preferably 5 mass% or less, more preferably 4.5 mass% or less, even more preferably 4 mass% or less, even more preferably 3.5 mass% or less, and particularly preferably 3.2 mass% or less. The lower limit of the content is not particularly limited, but when the resin components in the resin composition are taken as 100 mass%, it may be, for example, 0 mass% or more, 0.01 mass% or more, 0.1 mass% or more, etc., preferably 2 mass% or more, more preferably 2.5 mass% or more, and particularly preferably 2.8 mass%.

[0186] <(H) Other Additives> The resin composition of the present invention may further contain any other additives (H) as a non-volatile component. Examples of such additives include radical polymerizable compounds having a vinylphenyl group, a (meth)acryloyl group, a maleimide group, etc.; radical polymerization initiators such as peroxide radical polymerization initiators and azo radical polymerization initiators; thermosetting resins other than epoxy resins such as epoxy acrylate resins, urethane acrylate resins, urethane resins, cyanate resins, benzoxazine resins, unsaturated polyester resins, melamine resins, and silicone resins; organic metal compounds such as organic copper compounds, organic zinc compounds, and organic cobalt compounds; colorants such as phthalocyanine blue, phthalocyanine green, iodine green, diazo yellow, crystal violet, titanium oxide, and carbon black; polymerization inhibitors such as hydroquinone, catechol, pyrogallol, and phenothiazine; leveling agents such as silicone leveling agents and acrylic polymer leveling agents; thickeners such as bentone and montmorillonite; silicone defoamers, acrylic defoamers, fluorine defoamers, vinyl Antifoaming agents such as resin-based antifoaming agents; ultraviolet absorbers such as benzotriazole-based ultraviolet absorbers; adhesion improvers such as urea silane; adhesion promoters such as triazole-based adhesion promoters, tetrazole-based adhesion promoters, and triazine-based adhesion promoters; antioxidants such as hindered phenol-based antioxidants; fluorescent brighteners such as stilbene derivatives; surfactants such as fluorine-based surfactants and silicone-based surfactants; phosphorus-based flame retardants (e.g., phosphate ester compounds, phosphazene compounds, phosphinic acid compounds, red phosphorus Flame retardants such as butyl ether, nitrogen-based flame retardants (e.g., melamine sulfate), halogen-based flame retardants, and inorganic flame retardants (e.g., antimony trioxide); dispersants such as phosphate ester-based dispersants, polyoxyalkylene-based dispersants, acetylene-based dispersants, silicone-based dispersants, anionic dispersants, and cationic dispersants; stabilizers such as borate-based stabilizers, titanate-based stabilizers, aluminate-based stabilizers, zirconate-based stabilizers, isocyanate-based stabilizers, carboxylic acid-based stabilizers, and carboxylic anhydride-based stabilizers. (H) Other additives may be used alone or in combination of two or more at any ratio. The content of (H) other additives can be appropriately determined by those skilled in the art.

[0187] <(I) Organic solvent> The resin composition of the present invention may further contain an arbitrary organic solvent as a volatile component in addition to the non-volatile components described above. (I) As the organic solvent, a known one can be appropriately used, and the type is not particularly limited. (I) As the organic solvent, for example, ketone-based solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, etc.; ester-based solvents such as methyl acetate, ethyl acetate, butyl acetate, isobutyl acetate, isoamyl acetate, methyl propionate, ethyl propionate, γ-butyrolactone, etc.; ether-based solvents such as tetrahydrofuran, 1,4-dioxane, diethyl ether, diisopropyl ether, dibutyl ether, anisole, etc.; alcohol-based solvents such as methanol, ethanol, propanol, butanol, ethylene glycol, etc.; ether esters such as 2-ethoxyethyl acetate, propylene glycol monomethyl ether acetate, diethylene glycol monoethyl ether acetate, ethyl diglycol acetate, γ-butyrolactone, methyl methoxypropionate, etc. Examples of suitable organic solvents include ester-based solvents, ester alcohol-based solvents such as methyl lactate, ethyl lactate, and methyl 2-hydroxyisobutyrate, ether alcohol-based solvents such as 2-methoxypropanol, 2-methoxyethanol, 2-ethoxyethanol, propylene glycol monomethyl ether, and diethylene glycol monobutyl ether (butylcarbitol), amide-based solvents such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methyl-2-pyrrolidone, sulfoxide-based solvents such as dimethyl sulfoxide, nitrile-based solvents such as acetonitrile and propionitrile, aliphatic hydrocarbon-based solvents such as hexane, cyclopentane, cyclohexane, and methylcyclohexane, and aromatic hydrocarbon-based solvents such as benzene, toluene, xylene, ethylbenzene, and trimethylbenzene. (I) The organic solvent may be used alone or in any combination of two or more kinds at any ratio.

[0188] The content of the (I) organic solvent in the varnish-like resin composition before drying is not particularly limited, but is, for example, preferably 40% by mass or less, more preferably 30% by mass or less, even more preferably 20% by mass or less, and particularly preferably 10% by mass or less, when the total components in the resin composition are taken as 100% by mass. The content of the (I) organic solvent in the resin composition forming the resin composition layer after drying in the resin sheet is not particularly limited, but is preferably 5% by mass or less, more preferably 3% by mass or less, even more preferably 2% by mass or less, and particularly preferably 1% by mass or less, when the total components in the resin composition are taken as 100% by mass.

[0189] <Method of producing resin composition> The resin composition of the present invention can be produced, for example, by adding and mixing in any preparation vessel in any order and / or partially or completely simultaneously the following: (A) epoxy resin, (B) curing agent, (C) hollow inorganic filler having a porosity of 40 volume% or more, (D) imidazole-based curing accelerator having an active region including 130°C, and, if necessary, (C') solid inorganic filler, (E) stress relaxation component, (F) dimer acid skeleton-containing component, (G) thermoplastic resin, (H) other additives, and (I) organic solvent.

[0190] In addition, during the process of adding and mixing each component, the temperature can be appropriately set, and heating and / or cooling may be performed temporarily or throughout.

[0191] In addition, during or after the process of adding and mixing each component, the resin composition may be stirred or shaken using a stirring or shaking device such as a mixer to disperse the resin composition uniformly. In addition, degassing may be performed under low pressure conditions such as under vacuum at the same time as stirring or shaking.

[0192] <Characteristics of resin composition> The resin composition of the present invention contains (A) an epoxy resin, (B) a curing agent, (C) a hollow inorganic filler, and (D) an imidazole-based curing accelerator, in which the porosity of the (C) hollow inorganic filler is 40% by volume or more, the active region of the (D) imidazole-based curing accelerator includes 130° C., and the resin composition is (i) subjected to a first-stage heat curing at a curing temperature of less than 150° C., after which the reaction rate of the (A) epoxy resin is 15% or more and 70% or less, and (ii) subjected to a second-stage heat curing at a curing temperature of 150° C. or more, after which the reaction rate of the (A) epoxy resin is 85% or more. By using such a resin composition, an insulating layer having excellent surface flatness can be obtained, and the transmission loss in the circuit board can be reduced.

[0193] In one embodiment, the resin composition of the present invention can be characterized in that it can provide an insulating layer with excellent surface flatness. In one embodiment, when an insulating layer is formed using the resin composition of the present invention on an inner layer circuit board having a conductor circuit formed in a lattice wiring pattern as in the following Examples 1 to 7, the number of depressions with a side length of 50 to 150 μm in any 10 cm×10 cm area on the surface of the insulating layer can be 29 or less, preferably 9 or less.

[0194] In one embodiment, the cured product of the resin composition of the present invention can have a low dielectric constant. In one example, the dielectric constant of the cured product measured at a frequency of 5.8 GHz and a temperature of 90° C. by a cavity resonance perturbation method is preferably less than 3.3, more preferably 3.0 or less, particularly preferably 2.9 or less, and less than 2.8. There is no particular limit to the lower limit, and it can be, for example, 2.0 or more. The dielectric constant can be measured according to the method described in the examples below.

[0195] In one embodiment, the resin composition of the present invention can form an insulating layer having a small surface roughness after roughening treatment. For example, when a cured product (insulating layer) is formed using the resin composition of the present invention and then roughening treatment is performed as in the following Examples 1 to 7, the surface arithmetic average roughness Ra of the insulating layer can be preferably 200 nm or less, more preferably 150 nm or less, further preferably 14 nm or less, 120 nm or less, or 100 nm or less.

[0196] In one embodiment, the resin composition of the present invention can form an insulating layer having excellent adhesion to a plated conductor layer. In one example, the adhesion (peel strength) of the cured product (insulating layer) formed using the resin composition of the present invention to a plated conductor layer is preferably 0.40 kgf / cm or more, more preferably 0.45 kgf / cm or more, and particularly preferably 0.50 kgf / cm or more. There is no particular upper limit, and it may be, for example, 0.80 kgf / cm or less. The peel strength can be measured according to the method described in the examples below.

[0197] <Applications of resin composition> The resin composition of the present invention can be suitably used as a resin composition for forming an insulating layer of a printed wiring board (resin composition for insulating layer of printed wiring board), and more suitably used as a resin composition for forming an interlayer insulating layer of a printed wiring board (resin composition for insulating layer of printed wiring board). The resin composition of the present invention can also be suitably used when the printed wiring board is a circuit board with built-in components. The resin composition of the present invention can also be suitably used as a resin composition for forming an insulating layer of a rewiring board of a semiconductor package (resin composition for insulating layer of rewiring board). In the present invention, the printed wiring board and the rewiring board are collectively referred to as "circuit board", and therefore the resin composition of the present invention can be suitably used for the insulating layer of a circuit board.

[0198] The resin composition of the present invention can also be used in a wide range of applications requiring a resin composition, such as sheet-like laminate materials such as resin sheets and prepregs, solder resists, underfill materials, die bonding materials, semiconductor encapsulating materials, hole filling resins, and component embedding resins.

[0199] <Sheet-type laminated material> The resin composition of the present invention can be used by coating in the form of a varnish, but from an industrial perspective, it is generally preferred to use the resin composition in the form of a sheet-like laminate material containing the resin composition.

[0200] As the sheet-like laminate material, the following resin sheets and prepregs are preferred.

[0201] In one embodiment, the resin sheet includes a support and a resin composition layer provided on the support, and the resin composition layer is formed from the resin composition of the present invention.

[0202] The thickness of the resin composition layer is preferably 50 μm or less, more preferably 40 μm or less, from the viewpoint of making the printed wiring board thinner and being able to provide a cured product with excellent insulation even if the cured product of the resin composition is a thin film. The lower limit of the thickness of the resin composition layer is not particularly limited, but can usually be 5 μm or more, 10 μm or more, etc.

[0203] Examples of the support include films made of plastic materials, metal foils, and release papers, with films made of plastic materials and metal foils being preferred.

[0204] When a film made of a plastic material is used as the support, examples of the plastic material include polyesters such as polyethylene terephthalate (PET) and polyethylene naphthalate (PEN), polycarbonate (PC), acrylics such as polymethyl methacrylate (PMMA), cyclic polyolefins, triacetyl cellulose (TAC), polyether sulfide (PES), polyether ketone, polyimide, etc. Among these, polyethylene terephthalate and polyethylene naphthalate are preferred, and inexpensive polyethylene terephthalate is particularly preferred.

[0205] When a metal foil is used as the support, examples of the metal foil include copper foil, aluminum foil, etc., and copper foil is preferred. As the copper foil, a foil made of a single metal, copper, or an alloy of copper and another metal (e.g., tin, chromium, silver, magnesium, nickel, zirconium, silicon, titanium, etc.) may be used.

[0206] The support may be subjected to a matte treatment, a corona treatment, or an antistatic treatment on the surface to be bonded to the resin composition layer. In addition, a support with a release layer having a release layer on the surface to be bonded to the resin composition layer may be used as the support. The release agent used in the release layer of the support with a release layer may be, for example, one or more release agents selected from the group consisting of alkyd resins, polyolefin resins, urethane resins, and silicone resins. The support with a release layer may be a commercially available product, for example, "SK-1", "AL-5", and "AL-7" manufactured by Lintec Corporation, "Lumirror T60" manufactured by Toray Industries, Inc., "Purex" manufactured by Teijin Limited, and "Unipeel" manufactured by Unitika Limited, which are PET films having a release layer mainly composed of an alkyd resin-based release agent.

[0207] The thickness of the support is not particularly limited, but is preferably in the range of 5 μm to 75 μm, and more preferably in the range of 10 μm to 60 μm. When a support with a release layer is used, it is preferable that the total thickness of the support with a release layer is in the above range.

[0208] When a metal foil is used as the support, a metal foil with a support substrate may be used, which is a thin metal foil with a peelable support substrate attached thereto. In one embodiment, the metal foil with a support substrate includes a support substrate, a release layer provided on the support substrate, and a metal foil provided on the release layer. When a metal foil with a support substrate is used as the support, the resin composition layer is provided on the metal foil.

[0209] In the metal foil with a supporting substrate, the material of the supporting substrate is not particularly limited, and examples thereof include copper foil, aluminum foil, stainless steel foil, titanium foil, copper alloy foil, etc. When copper foil is used as the supporting substrate, it may be electrolytic copper foil or rolled copper foil. In addition, the release layer is not particularly limited as long as it can release the metal foil from the supporting substrate, and examples thereof include an alloy layer of an element selected from the group consisting of Cr, Ni, Co, Fe, Mo, Ti, W, and P; an organic coating, etc.

[0210] In the metal foil with a supporting substrate, the material of the metal foil is preferably, for example, copper foil or copper alloy foil.

[0211] In the metal foil with a supporting substrate, the thickness of the supporting substrate is not particularly limited, but is preferably in the range of 10 μm to 150 μm, more preferably in the range of 10 μm to 100 μm, and the thickness of the metal foil may be, for example, in the range of 0.1 μm to 10 μm.

[0212] In one embodiment, the resin sheet may further include an optional layer as necessary. For example, such an optional layer may be a protective film equivalent to the support provided on the surface of the resin composition layer that is not bonded to the support (i.e., the surface opposite to the support). The thickness of the protective film is not particularly limited, but is, for example, 1 μm to 40 μm. By laminating the protective film, adhesion of dirt and the like to the surface of the resin composition layer and scratches can be suppressed.

[0213] The resin sheet can be produced, for example, by applying a liquid resin composition onto a support using a die coater or the like, and drying the applied composition to form a resin composition layer.

[0214] The organic solvent may be the same as the organic solvent described as a component of the resin composition. The organic solvent may be used alone or in combination of two or more kinds.

[0215] Drying may be performed by a known method such as heating or hot air blowing. Drying conditions are not particularly limited, but drying is performed so that the content of the organic solvent in the resin composition layer becomes 10% by mass or less, preferably 5% by mass or less. Although it varies depending on the boiling point of the organic solvent in the resin composition or resin varnish, for example, when a resin composition or resin varnish containing 30% by mass to 60% by mass of the organic solvent is used, the resin composition layer can be formed by drying at 50°C to 150°C for 3 minutes to 10 minutes.

[0216] The resin sheet can be stored in a rolled state. When the resin sheet has a protective film, it can be used by peeling off the protective film.

[0217] In one embodiment, the prepreg is formed by impregnating a sheet-like fiber substrate with the resin composition of the present invention.

[0218] The sheet-like fiber substrate used for the prepreg is not particularly limited, and can be a substrate commonly used for prepreg, such as glass cloth, aramid nonwoven fabric, or liquid crystal polymer nonwoven fabric. From the viewpoint of thinning the circuit board, the thickness of the sheet-like fiber substrate is preferably 50 μm or less, more preferably 40 μm or less, even more preferably 30 μm or less, and particularly preferably 20 μm or less. The lower limit of the thickness of the sheet-like fiber substrate is not particularly limited. It is usually 10 μm or more.

[0219] The prepreg can be produced by a known method such as a hot melt method or a solvent method.

[0220] The thickness of the prepreg may be in the same range as that of the resin composition layer in the above-mentioned resin sheet.

[0221] The sheet-like laminate material of the present invention can be suitably used to form an insulating layer of a printed wiring board (for the insulating layer of a printed wiring board), and can be more suitably used to form an interlayer insulating layer of a printed wiring board (for the insulating layer of a printed wiring board). The sheet-like laminate material of the present invention can also be suitably used to form an insulating layer of a rewiring board of a semiconductor package (for the insulating layer of a rewiring board). That is, the sheet-like laminate material of the present invention can be suitably used as an insulating layer of a circuit board.

[0222] [Circuit board] The resin composition of the present invention can be used to form an insulating layer of a circuit board. The present invention also provides such a circuit board, i.e., a circuit board comprising a cured product of the resin composition of the present invention.

[0223] <Printed wiring board> In one embodiment, the circuit board of the present invention is a printed wiring board.

[0224] The printed wiring board can be produced, for example, by using the above-mentioned resin sheet, by a method including the following steps (I) and (II). (I) A step of laminating a resin sheet on an inner layer substrate such that a resin composition layer of the resin sheet is bonded to the inner layer substrate. (II) A step of curing (e.g., heat curing) the resin composition layer to form an insulating layer.

[0225] The "inner layer substrate" used in step (I) is a member that becomes the substrate of the printed wiring board, and examples thereof include a glass epoxy substrate, a metal substrate, a polyester substrate, a polyimide substrate, a BT resin substrate, and a thermosetting polyphenylene ether substrate. The substrate may have a conductor layer on one or both sides, and the conductor layer may be patterned. An inner layer substrate having a conductor layer (circuit) formed on one or both sides of the substrate may be called an "inner layer circuit substrate". In addition, an intermediate product on which an insulating layer and / or a conductor layer is to be formed during the manufacture of a printed wiring board is also included in the "inner layer substrate" of the present invention. When the printed wiring board is a circuit board with built-in components, an inner layer substrate with built-in components may be used.

[0226] The lamination of the inner layer substrate and the resin sheet can be carried out, for example, by thermocompression bonding the resin sheet to the inner layer substrate from the support side. Examples of the member for thermocompression bonding the resin sheet to the inner layer substrate (hereinafter also referred to as the "thermocompression bonding member") include a heated metal plate (such as a SUS plate) or a metal roll (SUS roll). The thermocompression bonding member may be pressed directly onto the resin sheet, or may be pressed via an elastic material such as heat-resistant rubber so that the resin sheet can sufficiently follow the surface irregularities of the inner layer substrate.

[0227] The lamination of the inner layer substrate and the resin sheet may be performed by a vacuum lamination method. In the vacuum lamination method, the thermocompression temperature is preferably in the range of 60°C to 160°C, more preferably in the range of 80°C to 140°C, the thermocompression pressure is preferably in the range of 0.098MPa to 1.77MPa, more preferably in the range of 0.29MPa to 1.47MPa, and the thermocompression time is preferably in the range of 20 seconds to 400 seconds, more preferably in the range of 30 seconds to 300 seconds. The lamination may be performed under reduced pressure conditions, preferably at a pressure of 26.7hPa or less.

[0228] The lamination can be performed by a commercially available vacuum laminator, such as a vacuum pressure laminator manufactured by Meiki Seisakusho Co., Ltd., a vacuum applicator manufactured by Nikko Materials Co., Ltd., or a batch type vacuum pressure laminator.

[0229] After lamination, the laminated resin sheet may be smoothed under normal pressure (atmospheric pressure), for example, by pressing a thermocompression member from the support side. The pressing conditions for the smoothing treatment may be the same as the thermocompression conditions for the lamination. The smoothing treatment may be performed using a commercially available laminator. The lamination and smoothing treatment may be performed consecutively using the commercially available vacuum laminator.

[0230] The support may be removed between step (I) and step (II), or after step (II). When a metal foil is used as the support, the conductor layer may be formed using the metal foil without peeling off the support. When a metal foil with a support substrate is used as the support, the support substrate (and the peel layer) may be peeled off. Then, the conductor layer can be formed using the metal foil.

[0231] In step (II), the resin composition layer is cured (for example, thermally cured) to form an insulating layer made of a cured product of the resin composition. The curing conditions for the resin composition layer are not particularly limited, and conditions that are usually adopted when forming an insulating layer for a printed wiring board may be used.

[0232] For example, the thermal curing conditions for the resin composition layer vary depending on the type of resin composition, etc., but in one embodiment, the curing temperature is preferably 140° C. to 250° C., more preferably 150° C. to 240° C., and even more preferably 170° C. to 230° C. The curing time can be preferably 5 minutes to 240 minutes, more preferably 10 minutes to 150 minutes, and even more preferably 15 minutes to 120 minutes.

[0233] Before the resin composition layer is thermally cured, the resin composition layer may be preheated at a temperature lower than the curing temperature. For example, prior to thermally curing the resin composition layer, the resin composition layer may be preheated at a temperature of 50° C. to 140° C., preferably 60° C. to 135° C., more preferably 70° C. to 130° C. for 5 minutes or more, preferably 5 minutes to 150 minutes, more preferably 15 minutes to 120 minutes, and even more preferably 15 minutes to 100 minutes.

[0234] In manufacturing a printed wiring board, the steps of (III) drilling holes in the insulating layer, (IV) roughening the insulating layer, and (V) forming a conductor layer may be further carried out. These steps (III) to (V) may be carried out according to various methods known to those skilled in the art that are used in manufacturing printed wiring boards. When the support is removed after step (II), the removal of the support may be carried out between step (II) and step (III), between step (III) and step (IV), or between step (IV) and step (V). In addition, the formation of the insulating layer and the conductor layer in steps (I) to (V) may be repeated to form a multilayer wiring board, as necessary.

[0235] In another embodiment, the printed wiring board of the present invention can be manufactured using the above-mentioned prepreg. The manufacturing method is basically the same as when a resin sheet is used.

[0236] Step (III) is a step of drilling holes in the insulating layer, which allows holes such as via holes and through holes to be formed in the insulating layer. Step (III) may be performed using, for example, a drill, a laser, plasma, etc., depending on the composition of the resin composition used to form the insulating layer. The dimensions and shape of the holes may be appropriately determined depending on the design of the printed wiring board.

[0237] Step (IV) is a step of roughening the insulating layer. Usually, in this step (IV), smear removal (desmear) is also performed. The procedure and conditions of the roughening treatment are not particularly limited, and known procedures and conditions that are usually used when forming an insulating layer of a printed wiring board can be adopted. For example, the insulating layer can be roughened by performing a swelling treatment with a swelling liquid, a roughening treatment with an oxidizing agent, and a neutralization treatment with a neutralizing liquid in this order.

[0238] The swelling liquid used in the roughening treatment is not particularly limited, but includes an alkaline solution, a surfactant solution, etc., and is preferably an alkaline solution, and more preferably a sodium hydroxide solution or a potassium hydroxide solution. Examples of commercially available swelling liquids include "Swelling Dip Securigans P" and "Swelling Dip Securigans SBU" manufactured by Atotech Japan. The swelling treatment using the swelling liquid is not particularly limited, but can be performed by immersing the insulating layer in a swelling liquid at 30°C to 90°C for 1 to 20 minutes, for example. From the viewpoint of suppressing the swelling of the resin of the insulating layer to an appropriate level, it is preferable to immerse the insulating layer in a swelling liquid at 40°C to 80°C for 5 to 15 minutes.

[0239] The oxidizing agent used in the roughening treatment is not particularly limited, but examples thereof include an alkaline permanganate solution in which potassium permanganate or sodium permanganate is dissolved in an aqueous solution of sodium hydroxide. The roughening treatment using an oxidizing agent such as an alkaline permanganate solution is preferably performed by immersing the insulating layer in an oxidizing agent solution heated to 60°C to 100°C for 10 minutes to 30 minutes. The concentration of permanganate in the alkaline permanganate solution is preferably 5% by mass to 10% by mass. Examples of commercially available oxidizing agents include alkaline permanganate solutions such as "Concentrate Compact CP" and "Dosing Solution Securigans P" manufactured by Atotech Japan.

[0240] The neutralizing solution used in the roughening treatment is preferably an acidic aqueous solution, and a commercially available product such as "Reduction Solution Securigant P" manufactured by Atotech Japan can be mentioned.

[0241] The treatment with the neutralizing solution can be carried out by immersing the surface that has been roughened with an oxidizing agent in a neutralizing solution at 30° C. to 80° C. for 5 to 30 minutes. From the viewpoint of workability, etc., a method in which the object that has been roughened with an oxidizing agent is immersed in a neutralizing solution at 40° C. to 70° C. for 5 to 20 minutes is preferred.

[0242] Step (V) is a step of forming a conductor layer, and the conductor layer is formed on the insulating layer. The conductor material used for the conductor layer is not particularly limited. In a preferred embodiment, the conductor layer contains one or more metals selected from the group consisting of gold, platinum, palladium, silver, copper, aluminum, cobalt, chromium, zinc, nickel, titanium, tungsten, iron, tin and indium. The conductor layer may be a single metal layer or an alloy layer, and examples of the alloy layer include layers formed from alloys of two or more metals selected from the above group (e.g., nickel-chromium alloy, copper-nickel alloy and copper-titanium alloy). Among these, from the viewpoints of versatility in forming the conductor layer, cost, ease of patterning, and the like, a single metal layer of chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver, or copper, or an alloy layer of a nickel-chromium alloy, a copper-nickel alloy, or a copper-titanium alloy is preferred, a single metal layer of chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver, or copper, or an alloy layer of a nickel-chromium alloy is more preferred, and a single metal layer of copper is even more preferred.

[0243] The conductor layer may be a single-layer structure or a multi-layer structure in which two or more single metal layers or alloy layers made of different kinds of metals or alloys are laminated. When the conductor layer has a multi-layer structure, the layer in contact with the insulating layer is preferably a single metal layer of chromium, zinc or titanium, or an alloy layer of a nickel-chromium alloy.

[0244] The thickness of the conductor layer depends on the desired design of the printed wiring board, but is generally 3 μm to 35 μm, and preferably 5 μm to 30 μm.

[0245] In one embodiment, the conductor layer may be formed by plating. From the viewpoint of facilitating the formation of fine wiring, it is preferable to form the conductor layer by a semi-additive method. An example of forming the conductor layer by the semi-additive method will be described below.

[0246] First, a plating seed layer is formed on the surface of an insulating layer by electroless plating. Next, a mask pattern is formed on the formed plating seed layer to expose a part of the plating seed layer corresponding to a desired wiring pattern. After a metal layer is formed on the exposed plating seed layer by electrolytic plating, the mask pattern is removed. Thereafter, unnecessary plating seed layer is removed by etching or the like to form a conductor layer having a desired wiring pattern.

[0247] In another embodiment, the conductor layer may be formed using a metal foil. When the conductor layer is formed using a metal foil, it is preferable to carry out the step (V) between the steps (I) and (II). For example, after the step (I), the support is removed, and a metal foil is laminated on the exposed surface of the resin composition layer. The lamination of the resin composition layer and the metal foil may be carried out by a vacuum lamination method. The lamination conditions may be the same as those described for the step (I). Then, the step (II) is carried out to form an insulating layer. Thereafter, a conductor layer having a desired wiring pattern can be formed by a conventionally known technique such as a modified semi-additive method, using the metal foil on the insulating layer.

[0248] The metal foil can be produced by a known method such as an electrolytic method, a rolling method, etc. Commercially available metal foils include, for example, HLP foil and JXUT-III foil manufactured by JX Metals, and 3EC-III foil and TP-III foil manufactured by Mitsui Kinzoku Co., Ltd.

[0249] Alternatively, when a metal foil or a metal foil with a supporting substrate is used as the support for the resin sheet, the conductor layer may be formed using the metal foil, as described above.

[0250] <Rewiring substrate for semiconductor packages> In one embodiment, the circuit board of the present invention is a rewiring board (rewiring layer) of a semiconductor package. Hereinafter, a method for manufacturing a semiconductor package will be described.

[0251] The semiconductor package contains a cured product of the resin composition of the present invention as an insulating layer of a rewiring board. The semiconductor package may contain a cured product of the resin composition of the present invention as a sealing layer.

[0252] A semiconductor package can be manufactured, for example, by a method including the following steps (1) to (6) using the resin composition and resin sheet of the present invention. The resin composition and resin sheet of the present invention may be used to form a rewiring formation layer (insulating layer for forming a rewiring board) in step (5) or a sealing layer in step (3). An example of forming a rewiring formation layer or a sealing layer using a resin composition or a resin sheet is shown below, but the technology for forming a rewiring formation layer or a sealing layer of a semiconductor package is publicly known, and a person skilled in the art can manufacture a semiconductor package using the resin composition and resin sheet of the present invention according to a publicly known technology. (1) A step of laminating a temporary fixing film onto a substrate; (2) a step of temporarily fixing a semiconductor chip on a temporary fixing film; (3) forming an encapsulation layer on the semiconductor chip; (4) peeling the substrate and the temporary fixing film from the semiconductor chip; (5) forming a rewiring formation layer as an insulating layer on the surface of the semiconductor chip from which the base material and the temporary fixing film have been peeled off; and (6) A process of forming a rewiring layer as a conductor layer on the rewiring formation layer.

[0253] -Process (1)- The material used for the substrate is not particularly limited. Examples of the substrate include semiconductor wafers such as silicon wafers, glass wafers, glass substrates, metal substrates such as copper, titanium, stainless steel, and cold-rolled steel (SPCC), substrates in which glass fibers are impregnated with epoxy resin or the like and subjected to a heat curing treatment (e.g., FR-4 substrates), and substrates made of bismaleimide triazine resin (BT resin).

[0254] The material of the temporary fixing film is not particularly limited as long as it can be peeled off from the semiconductor chip in step (4) and can temporarily fix the semiconductor chip. A commercially available product can be used as the temporary fixing film. An example of the commercially available product is Riva Alpha manufactured by Nitto Denko Corporation.

[0255] -Process (2)- The semiconductor chips can be temporarily fixed using known devices such as a flip chip bonder, a die bonder, etc. The layout and number of semiconductor chips can be appropriately set depending on the shape and size of the temporary fixing film, the number of semiconductor packages to be produced, etc., and for example, the semiconductor chips can be temporarily fixed by arranging them in a matrix shape of multiple rows and multiple columns.

[0256] -Process (3)- A resin composition layer of the resin sheet of the present invention is laminated on a semiconductor chip, or the resin composition of the present invention is applied onto a semiconductor chip and cured (for example, thermally cured) to form an encapsulating layer.

[0257] For example, the semiconductor chip and the resin sheet can be laminated by removing the protective film of the resin sheet and then heat-pressing the resin sheet to the semiconductor chip from the support side. Examples of the member for heat-pressing the resin sheet to the semiconductor chip (hereinafter also referred to as the "heat-pressing member") include a heated metal plate (such as a SUS plate) or a metal roll (SUS roll). It is preferable to press the heat-pressing member not directly onto the resin sheet but via an elastic material such as heat-resistant rubber so that the resin sheet can sufficiently follow the surface irregularities of the semiconductor chip. The semiconductor chip and the resin sheet may be laminated by a vacuum lamination method, and the lamination conditions are the same as those described in relation to the manufacturing method of the printed wiring board, and the preferred ranges are also the same.

[0258] After lamination, the resin composition is thermally cured to form the encapsulating layer under the same conditions as those described in relation to the method for producing a printed wiring board.

[0259] The support of the resin sheet may be peeled off after the resin sheet is laminated on the semiconductor chip and thermally cured, or the support may be peeled off before the resin sheet is laminated on the semiconductor chip.

[0260] When the resin composition of the present invention is applied to form a sealing layer, the application conditions are the same as the application conditions when forming the resin composition layer described in relation to the resin sheet of the present invention, and the preferred ranges are also the same.

[0261] -Process (4)- The method for peeling off the substrate and the temporary fixing film can be appropriately changed depending on the material of the temporary fixing film, and examples of the method include a method in which the temporary fixing film is heated and foamed (or expanded) to peel it off, and a method in which ultraviolet light is irradiated from the substrate side to reduce the adhesive strength of the temporary fixing film and then peeled off.

[0262] In the method of heating and foaming (or expanding) the temporary fixing film to peel it off, the heating conditions are usually 100 to 250° C. for 1 to 90 seconds or 5 to 15 minutes. In the method of irradiating ultraviolet light from the substrate side to reduce the adhesive strength of the temporary fixing film to peel it off, the irradiation dose of ultraviolet light is usually 10 mJ / cm. 2 ~1000mJ / cm 2 It is.

[0263] -Process (5)- The resin composition and resin sheet of the present invention are used to form a rewiring formation layer (insulating layer of a rewiring board).

[0264] After forming the redistribution layer, a via hole may be formed in the redistribution layer to connect the semiconductor chip to a conductor layer described later. The via hole may be formed by a known method depending on the material of the redistribution layer.

[0265] -Process (6)- The formation of the conductor layer on the rewiring formation layer may be carried out in the same manner as in step (V) described in relation to the method for producing a printed wiring board. Note that steps (5) and (6) may be repeated to alternately stack (build up) the conductor layer (rewiring layer) and the rewiring formation layer (insulating layer).

[0266] In manufacturing the semiconductor package, the steps of (7) forming a solder resist layer on the conductor layer (rewiring layer), (8) forming bumps, and (9) dicing a plurality of semiconductor packages into individual semiconductor packages may be further carried out. These steps may be carried out according to various methods used in manufacturing semiconductor packages and known to those skilled in the art.

[0267] By forming a rewiring formation layer (insulating layer) using the resin composition and resin sheet of the present invention, which can provide an insulating layer that has excellent surface flatness and plating adhesion, as well as a low relative dielectric constant and can reduce transmission loss, a semiconductor package with extremely low transmission loss can be realized regardless of whether the semiconductor package is a fan-in (Fan-In) type package or a fan-out (Fan-Out) type package. In one embodiment, the semiconductor package of the present invention is a fan-out (Fan-Out) type package. The resin composition and resin sheet of the present invention can be applied regardless of whether the semiconductor package is a fan-out type panel level package (FOPLP) or a fan-out type wafer level package (FOWLP). In one embodiment, the semiconductor package of the present invention is a fan-out type panel level package (FOPLP) or a fan-out type wafer level package (FOWLP).

[0268] [Semiconductor Devices] The semiconductor device of the present invention includes a cured product of the resin composition of the present invention. The semiconductor device of the present invention can be produced by using the circuit board of the present invention.

[0269] Examples of the semiconductor device include various semiconductor devices used in electric appliances (for example, computers, mobile phones, digital cameras, and televisions) and vehicles (for example, motorcycles, automobiles, trains, ships, and aircraft). EXAMPLES

[0270] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. In the following, "parts" and "%" representing amounts mean "parts by mass" and "% by mass", respectively, unless otherwise specified. Unless otherwise specified, the temperature conditions, pressure conditions, and humidity conditions are room temperature (25°C), atmospheric pressure (1 atm), and 50% RH.

[0271] [Preparation of resin sheet] First, the resin sheets of the examples and comparative examples will be described. The resin sheets are an example of the sheet-like laminate material of the present invention.

[0272] <Example 1> Thirty parts of a bisphenol A type epoxy resin ("828US" manufactured by Mitsubishi Chemical Corporation, epoxy equivalent: approximately 180) and 30 parts of a biphenyl type epoxy resin ("NC3000H" manufactured by Nippon Kayaku Co., Ltd., epoxy equivalent: approximately 269) were heated and dissolved in 55 parts of solvent naphtha with stirring, and then cooled to room temperature. To the mixed solution, 60 parts of hollow inorganic filler (average particle size 0.5 μm, porosity 50 volume%, Ube Exsymo Corp. "LHP-208") that had been surface-treated with an aminosilane coupling agent (Shin-Etsu Chemical Co., Ltd. "KBM573"), 140 parts of solid inorganic filler (average particle size 0.5 μm, Admatechs Corp. "SO-C2") that had been surface-treated with an aminosilane coupling agent "KBM573", and 3 parts of methacryl butadiene styrene rubber particles (Dow Chemical Japan "EXL-2655") were added, and the mixture was kneaded with a three-roll mill to uniformly disperse the mixture. The roll dispersion was mixed with 14 parts of a triazine skeleton-containing phenolic hardener (DIC Corporation's "LA-3018-50P", hydroxyl group equivalent of about 151, 1-methoxy-2-propanol solution with a solid content of 50%), 40 parts of an active ester compound (DIC Corporation's "HPC-8000-65T", active group equivalent of about 223, toluene solution with a non-volatile content of 65% by mass), and 10 parts of a phenoxy resin (Mitsubishi Chemical Corporation's "YX6954BH30 A resin varnish was prepared by mixing 10 parts of a curing accelerator ("DMAP", a mixed solution of MEK and cyclohexanone with a solids content of 30%), 2 parts of a curing accelerator ("1B2PZ", manufactured by Shikoku Chemical Industry Co., Ltd., 1-benzyl-2-phenylimidazole, a 1-methoxy-2-propanol solution with a solids content of 10% by mass), and dispersing the mixture uniformly using a high-speed rotating mixer. A PET film with an alkyd resin-based release layer ("AL5" manufactured by Lintec Corporation, thickness 38 μm) was prepared as a support. A resin varnish was uniformly applied onto the release layer of the support so that the thickness of the resin composition layer after drying was 40 μm, and the resin sheet was produced by drying at 80 to 120° C. (average 100° C.) for 5 minutes.

[0273] <Example 2> A resin varnish was prepared in the same manner as in Example 1, except that 3 parts of the methacryl butadiene styrene rubber particles "EXL-2655" in Example 1 were replaced with 3 parts of an epoxidized polybutadiene resin ("PB3600" manufactured by Daicel Corporation), and a resin sheet was produced.

[0274] <Example 3> A resin varnish was prepared in the same manner as in Example 1, except that 3 parts of the methacryl butadiene styrene rubber particles "EXL-2655" in Example 1 was changed to 3 parts of a maleimide resin having a carbon skeleton derived from dimer acid ("BMI689" manufactured by Designer Molecules) as a dimer acid skeleton-containing component, and a resin sheet was produced.

[0275] <Example 4> A resin varnish was prepared in the same manner as in Example 1, except that the 2 parts of the curing accelerator "DMAP" in Example 1 was changed to 0 parts, and the 2 parts of the curing accelerator "1B2PZ" was changed to 5 parts, and a resin sheet was produced.

[0276] <Example 5> In Example 1, 2 parts of the curing accelerator "DMAP" was changed to 0 parts, 2 parts of the curing accelerator "1B2PZ" was changed to 4 parts, and 0 parts of the curing accelerator ("C11Z-A" manufactured by Shikoku Chemical Industry Co., Ltd., 2,4-diamino-6-[2'-undecylimidazolyl-(1')]-ethyl-s-triazine, 1-methoxy-2-propanol solution with a solid content of 10% by mass) was changed to 2 parts. Except for this, a resin varnish was prepared in the same manner as in Example 1, and a resin sheet was produced.

[0277] <Example 6> A resin varnish was prepared in the same manner as in Example 1, except that the hollow inorganic filler "LHP-208" surface-treated with the aminosilane coupling agent "KBM573" in Example 1 was changed from 60 parts to 90 parts, the solid inorganic filler "SO-C2" surface-treated with the aminosilane coupling agent "KBM573" was changed from 140 parts to 80 parts, and 3 parts of a maleimide resin "BMI689" having a carbon skeleton derived from dimer acid were added. A resin sheet was produced in the same manner as in Example 1.

[0278] <Example 7> A resin varnish was prepared in the same manner as in Example 1, except that 3 parts of the methacryl butadiene styrene rubber particles "EXL-2655" in Example 1 was changed to 0 parts, and a resin sheet was produced. <Example 8> In Example 1, 60 parts of hollow inorganic filler (average particle size 0.5 μm, porosity 50 volume%, hollow silica "LHP-208" manufactured by Ube Exximo Co., Ltd.) surface-treated with an aminosilane coupling agent ("KBM573" manufactured by Shin-Etsu Chemical Co., Ltd.) was changed to 0 parts, and 24 parts of hollow inorganic filler (average particle size 1.6 μm, porosity 80 volume%, hollow aluminosilicate particles "MGH-500" manufactured by Pacific Cement Co., Ltd.) surface-treated with an aminosilane coupling agent ("KBM573" manufactured by Shin-Etsu Chemical Co., Ltd.) was added. Except for this, a resin varnish was prepared in the same manner as in Example 1, and a resin sheet was produced. <Example 9> In Example 1, 60 parts of hollow inorganic filler (average particle size 0.5 μm, porosity 50 volume%, Ube Exximo Co., Ltd. "LHP-208") surface-treated with an aminosilane coupling agent (Shin-Etsu Chemical Co., Ltd. "KBM573") was changed to 0 parts, and 30 parts of hollow inorganic filler (average particle size 2.0 μm, porosity 75 volume%, AGC Co., Ltd. hollow silica "HS-200") surface-treated with an aminosilane coupling agent (Shin-Etsu Chemical Co., Ltd. "KBM573") was added. Except for this, a resin varnish was prepared in the same manner as in Example 1, and a resin sheet was produced.

[0279] <Comparative Example 1> A resin varnish was prepared in the same manner as in Example 4, except that the curing accelerator "1B2PZ" in Example 4 was changed from 5 parts to 0 parts, and a resin sheet was produced.

[0280] <Comparative Example 2> A resin varnish was prepared in the same manner as in Example 1, except that the 2 parts of the curing accelerator "1B2PZ" in Example 1 was changed to 0 parts, and the 2 parts of the curing accelerator "DMAP" was changed to 6 parts, and a resin sheet was produced.

[0281] <Comparative Example 3> A resin varnish was prepared in the same manner as in Example 1, except that 2 parts of a curing accelerator ("2E4MZ" manufactured by Shikoku Chemical Industry Co., Ltd., 2-ethyl-4-methylimidazole, 1-methoxy-2-propanol solution with a solid content of 10% by mass) was added instead of 2 parts of the curing accelerator "1B2PZ" in Example 1, and a resin sheet was produced.

[0282] <Comparative Example 4> A resin varnish was prepared in the same manner as in Example 1, except that 2 parts of the curing accelerator "1B2PZ" in Example 1 was changed to 2 parts of a curing accelerator ("2PZ-CN" manufactured by Shikoku Chemical Industry Co., Ltd., 1-(2-cyanoethyl)-2-phenylimidazole, 1-methoxy-2-propanol solution with a solid content of 10% by mass). A resin sheet was produced.

[0283] <Comparative Example 5> In Example 1, the active ester compound "HPC-8000-65T" was changed from 40 parts to 0 parts, the hollow inorganic filler "LHP-208" surface-treated with the aminosilane coupling agent "KBM573" was changed from 60 parts to 48 parts, the solid inorganic filler "SO-C2" surface-treated with the aminosilane coupling agent "KBM573" was changed from 140 parts to 112 parts, the curing accelerator "DMAP" was changed from 2 parts to 12 parts, and the curing accelerator "1B2PZ" was changed from 2 parts to 0 parts. Except for this, a resin varnish was prepared in the same manner as in Example 1, and a resin sheet was produced.

[0284] Subsequently, various measurements were carried out using the resin sheets (resin composition layer thickness: 40 μm) produced in Examples 1 to 7 and Comparative Examples 1 to 5. The methods of the various measurements and the results thereof will be described below.

[0285] [1. Arithmetic mean roughness (Ra)] The resin sheets produced in Examples 1 to 7 and Comparative Examples 1 to 5 were laminated on an inner layer circuit board 1 to produce a measurement board (hereinafter also referred to as "evaluation sample a"), and the arithmetic mean roughness (Ra) of the surface of each evaluation sample a was measured.

[0286] <Preparation of measurement substrate (evaluation sample a)> (1-1) Surface treatment of inner layer circuit board 1 Both sides of a glass cloth-based epoxy resin double-sided copper-clad laminate (copper foil thickness 18 μm, substrate thickness 0.8 mm, Panasonic Corporation's "R1766") (so-called inner layer circuit board 1) on which an inner layer circuit was formed was etched by 1.0 μm using MEC Corporation's "CZ8101" to roughen the copper surface. The inner layer circuit boards 1 were prepared in a number corresponding to the resin sheets produced in Examples 1 to 7 and Comparative Examples 1 to 5, and were subjected to surface treatment.

[0287] (1-2) Lamination of resin sheets The resin sheets prepared in Examples 1 to 7 and Comparative Examples 1 to 5 were laminated on the inner circuit board 1 that had been subjected to the surface treatment in the above-mentioned (1-1) treatment, respectively, in the following procedure. Specifically, two resin sheets were prepared, and one resin sheet was arranged so that the resin composition layer of the resin sheet faced the upper surface of the inner circuit board 1, and the other resin sheet was arranged so that the resin composition layer of the resin sheet faced the lower surface of the inner circuit board 1. The inner circuit board 1 sandwiched between the two resin sheets was laminated using a batch-type vacuum pressure laminator (Nikko Materials Co., Ltd. "CVP700", a two-stage build-up laminator). The lamination was performed by reducing the pressure for 30 seconds to 13 hPa or less, and then pressing at 100°C and a pressure of 0.74 MPa for 30 seconds. Next, the inner circuit board 1 after the lamination treatment was heat-pressed at 100°C and a pressure of 0.5 MPa for 60 seconds.

[0288] (1-3) Curing of resin composition In the above-mentioned (1-2) treatment, after laminating resin sheets on both sides of the inner layer circuit board 1, the resin composition layer was heat-cured at 130°C for 30 minutes as the first heat curing step, and then the resin composition layer was heat-cured at 170°C for 30 minutes as the second heat curing step to form an insulating layer. Thereafter, the support was peeled off to expose the insulating layer. As a result, an inner layer circuit board 1 with the insulating layer exposed (hereinafter also referred to as "insulating layer exposed board 1") was obtained.

[0289] (1-4) Roughening treatment The inner layer circuit board 1 with the insulating layer exposed (so-called insulating layer exposed board 1) obtained by the above treatment (1-3) was immersed in a swelling liquid (Atotech Japan's "Swelling Dip Securigant P", an aqueous solution of sodium hydroxide containing diethylene glycol monobutyl ether) at 60°C for 10 minutes. Next, the insulating layer exposed board 1 was immersed in an oxidizing agent (Atotech Japan's "Concentrate Compact CP", an aqueous solution of potassium permanganate at about 6 mass% and sodium hydroxide at about 4 mass%) at 80°C for 20 minutes, and finally in a neutralizing liquid (Atotech Japan's "Reduction Solution Securigant P", an aqueous solution of hydroxylamine sulfate) at 40°C for 5 minutes. After that, the insulating layer exposed board 1 was dried at 80°C for 15 minutes. The obtained board is called "evaluation sample a".

[0290] <Measurement of arithmetic mean roughness (Ra)> For each of the evaluation samples a made using the resin sheets of Examples 1 to 7 and Comparative Examples 1 to 5, the Ra value was calculated using a non-contact surface roughness meter (Beeco Instruments' "WYKO NT3300") in VSI contact mode with a 50x lens to obtain a measurement range of 121 μm x 92 μm. The Ra value was calculated by calculating the average value of 10 randomly selected points. The measurement results are shown in Table 1 below.

[0291] [2. Peel strength] Next, a conductor layer was formed on evaluation samples a of Examples 1 to 7 and Comparative Examples 1 to 5 to prepare measurement substrates (hereinafter also referred to as "evaluation samples b"). The peel strength between the conductor layer and insulating layer of each evaluation sample b was measured.

[0292] <Preparation of measurement substrate (evaluation sample b)> (2-1) Formation of the conductor layer A conductor layer was formed on each of the evaluation samples a of Examples 1 to 7 and Comparative Examples 1 to 5 obtained in (1-4) above by a semi-additive method. Specifically, a conductor layer was formed on the roughened surface of the insulating layer of each evaluation sample a by carrying out a plating process including the following steps [1] to [6]. In the following steps [1] to [6], a chemical solution manufactured by Atotech Japan was used.

[0293] [1] Alkaline cleaning process In step [1], the surface of the insulating layer in which the via holes were provided was cleaned and the charge was adjusted. Specifically, the surface of the insulating layer of each evaluation sample a was cleaned at 60°C for 5 minutes using "Cleaning Cleaner Securiganth 902".

[0294] [2] Soft etching process In step [2], the inside of the via hole was cleaned. Specifically, each evaluation sample a that had been subjected to the alkaline cleaning in step [1] above was treated with an aqueous solution of sodium peroxodisulfate acidified with sulfuric acid at 30° C. for 1 minute.

[0295] [3] Pre-dip process In step [3], the surface charge of the insulating layer was adjusted as a pretreatment for the following step [4]. Specifically, each evaluation sample a that had been soft-etched in the above step [2] was immersed in "Pre. Dip Neoganth B" and treated at room temperature for 1 minute.

[0296] [4] Activator application process (application of Pd to the surface of the insulating layer) In step [4], an activator (here, Pd) was applied to the surface of the insulating layer. Specifically, each evaluation sample a pre-dipped in step [3] above was treated with "Activator Neoganth 834" at 35°C for 5 minutes.

[0297] [5] Reduction process In step [5], the Pd applied to the insulating layer in step [4] above was reduced. Specifically, each evaluation sample a treated in step [4] above was treated at 30°C for 5 minutes using a mixture of "Reducer Neoganth WA" and "Reducer Accelerator 810 mod."

[0298] [6] Electroless copper plating process (Cu is deposited on the surface of the insulating layer (Pd surface)) In step [6], copper (Cu) was deposited on the surface of the insulating layer of each evaluation sample a processed in step [5] above. Specifically, each evaluation sample a processed in step [4] above was treated at 35°C for 30 minutes using a mixture of "Basic Solution Printganth MSK-DK", "Copper solution Printganth MSK", "Stabilizer Printganth MSK-DK" and "Reducer Cu". The thickness of the electroless copper plating layer formed on the insulating layer was 1 μm.

[0299] Next, the substrate was heated at 150°C for 30 minutes for annealing, and then an etching resist was formed and a pattern was formed by etching. After that, copper sulfate electrolytic plating was performed using a chemical solution manufactured by Atotech Japan to form a conductor layer with a thickness of 25 μm, and an annealing treatment was performed at 200°C for 60 minutes. The obtained substrate is referred to as "evaluation sample b".

[0300] <Peel strength measurement> The peel strength between the insulating layer and the conductor layer was measured for the evaluation samples b of Examples 1 to 7 and Comparative Examples 1 to 5 in accordance with the Japanese Industrial Standards (JIS C6481). Specifically, the evaluation sample b was placed on a horizontal table, a 10 mm wide and 100 mm long cut was made in the conductor layer, one end of the cut was peeled off and held with a gripper, and the load (kgf / cm) (in other words, the peel strength) was measured when 35 mm was peeled off vertically at a speed of 50 mm / min at room temperature. A larger load indicates a higher adhesion between the insulating layer and the conductor layer (in other words, a higher plating adhesion). A tensile tester ("AC-50C-SL" manufactured by TSE Co., Ltd.) was used for the measurement. The measurement results are shown in Table 1 below.

[0301] [3. Dielectric constant] Next, the resin composition layers of the resin sheets produced in Examples 1 to 7 and Comparative Examples 1 to 5 were cured to prepare cured products for measurement (hereinafter also referred to as "evaluation samples c"), and the relative dielectric constant of each evaluation sample c was measured.

[0302] <Preparation of evaluation sample c> The resin sheets produced in Examples 1 to 7 and Comparative Examples 1 to 5 were each heated at 200° C. for 90 minutes to thermally cure the resin composition layers, and then the support was peeled off. The resulting cured products are referred to as “evaluation sample c.”

[0303] <Measurement of relative dielectric constant> The evaluation samples c of Examples 1 to 7 and Comparative Examples 1 to 5 were each cut into a test piece having a width of 2 mm and a length of 80 mm. The relative dielectric constant of the test pieces was measured by a cavity resonance perturbation method using an Agilent Technologies "HP8362B" at a measurement frequency of 5.8 GHz and a measurement temperature of 23°C. For each evaluation sample c, two test pieces were subjected to the measurement of the relative dielectric constant, and the average of the measured values ​​was calculated. The calculation results are shown in Table 1 below.

[0304] [4. Reaction rate of epoxy resin after the first heat curing step] Next, the first stage of thermal curing of the resin composition (layer) was carried out for each of the resin sheets of Examples 1 to 7 and Comparative Examples 1 to 5, and the reaction rate of the epoxy resin in the obtained cured product (hereinafter also referred to as "evaluation sample d") was calculated.

[0305] <Preparation of evaluation sample d> The resin sheets prepared in Examples 1 to 7 and Comparative Examples 1 to 5 were laminated onto a polyimide film (Ube Industries, Ltd., "Upilex S") using a batch-type vacuum pressure laminator (Nikko Materials Co., Ltd., "CVP700", a two-stage build-up laminator). The lamination process was carried out by reducing the pressure for 30 seconds to 13 hPa or less, and then pressing at 100°C and a pressure of 0.74 MPa for 30 seconds. Thereafter, the resin composition (layer) in each resin sheet was cured under the conditions of 130°C for 30 minutes as the first stage of thermal curing, and the polyimide film and the support were peeled off in sequence. The obtained cured product is referred to as "evaluation sample d". Note that for each of Examples 1 to 7 and Comparative Examples 1 to 5, a laminate of the resin sheet and the polyimide film before the first stage of thermal curing was prepared as a "control sample".

[0306] <Calculation of the reaction rate of the epoxy resin in the evaluation sample d> The evaluation samples d of Examples 1 to 7 and Comparative Examples 1 to 5 were each subjected to FT-IR ("FT / IR-4600" manufactured by JASCO, a Fourier transform infrared analyzer) to detect a predetermined peak derived from an epoxy group (specifically, a peak top of 4530 cm -1 ) and a certain peak due to the C-H bond of the aromatic ring (specifically, the peak top 4621 cm -1 and 4676 cm -1 Next, the intensity of a specific peak derived from an epoxy group (specifically, the peak area with a peak top of 4530 cm-1) of each evaluation sample d was measured, and the intensity of a specific peak derived from a C-H bond of an aromatic ring (specifically, the peak area with a peak top of 4621 cm-1) was measured. -1 and 4676 cm -1 The value was calculated by dividing the total area of ​​the peaks by the total area of ​​the peaks (the total area of ​​the peaks after the reaction) (hereinafter referred to as the "post-reaction divided value").

[0307] Similarly, the control samples of Examples 1 to 7 and Comparative Examples 1 to 5 were subjected to FT-IR to measure the intensities of the above-mentioned predetermined peaks derived from epoxy groups and predetermined peaks derived from aromatic rings. Next, the intensities of the predetermined peaks derived from epoxy groups of each control sample (specifically, the peak top at 4530 cm -1 The peak area of ​​the aromatic ring was calculated by dividing the intensity of a specific peak derived from the C-H bond (specifically, the peak top area of ​​4621 cm -1 and 4676 cm -1 The value was calculated by dividing the total area of ​​the peaks by the total area of ​​the peaks (the total area of ​​the peaks before the reaction) (hereinafter referred to as the "divided value before the reaction").

[0308] The reaction rate of the epoxy resin in each evaluation sample d was calculated by the following formula (2). The calculation results are shown in Table 1 below.

[0309] Reaction rate of epoxy resin = (1 - quotient after reaction / quotient before reaction) × 100 (2)

[0310] [5. Reaction rate of epoxy resin after the second heat curing stage] Next, for each of the resin sheets of Examples 1 to 7 and Comparative Examples 1 to 5, the resin composition (layer) was subjected to a first-stage thermal curing, and then a second-stage thermal curing, and the reaction rate of the epoxy resin in the obtained cured product (hereinafter also referred to as "evaluation sample e") was calculated.

[0311] <Preparation of evaluation sample e> The resin sheets prepared in Examples 1 to 7 and Comparative Examples 1 to 5 were laminated onto a polyimide film (Ube Industries, Ltd., "Upilex S") in the same manner as in the above <Preparation of Evaluation Sample d>, and after the first stage of heat curing, the resin composition was cured at 170°C for 30 minutes as the second stage of heat curing, and the polyimide film and the support were peeled off in sequence. The obtained cured products are referred to as "evaluation cured products e". "Control samples" of each evaluation cured product e were also prepared.

[0312] <Calculation of the reaction rate of the epoxy resin in the evaluation sample e> The reaction rate of the epoxy resin in the evaluation sample e was calculated in the same manner as in the above <Calculation of the reaction rate of the epoxy resin in the evaluation sample d>, except that the evaluation sample e was subjected to FT-IR. The calculation results are shown in Table 1 below.

[0313] [6.Surface flatness] Next, the resin sheets produced in Examples 1 to 7 and Comparative Examples 1 to 5 were laminated on an inner layer circuit board 2 to produce a measurement board (hereinafter also referred to as "evaluation sample f"), and the surface flatness of each evaluation sample f was evaluated.

[0314] <Preparation of measurement substrate (evaluation sample f)> (6-1) Surface treatment of inner layer circuit board 2 First, a glass cloth-based epoxy resin double-sided copper-clad laminate (copper foil thickness 12 μm, board thickness 0.8 mm, Panasonic "R1515A") (so-called inner layer circuit board 2) was prepared, which had a conductor circuit formed on both sides with a lattice-shaped wiring pattern (copper remaining rate 59%). Next, both sides of the inner layer circuit board 2 were subjected to a copper surface roughening treatment (copper etching amount 0.5 μm) using MEC's ​​"CZ8201". The inner layer circuit boards 2 were prepared in a number corresponding to the resin sheets produced in Examples 1 to 7 and Comparative Examples 1 to 5, and were subjected to a base treatment.

[0315] (6-2) Lamination of resin sheets The resin sheets produced in Examples 1 to 7 and Comparative Examples 1 to 5 were laminated on the inner layer circuit board 2 that had been subjected to surface treatment, respectively, in the following manner. Specifically, a batch-type vacuum pressure laminator (Nikko Materials Co., Ltd. "CVP700", a two-stage build-up laminator) was used to laminate both sides of the inner layer circuit board 2 so that the resin composition layer of the resin sheet was bonded to the inner layer circuit board 2. The lamination was performed by reducing the pressure for 30 seconds to 13 hPa or less, and then pressing at 100°C and a pressure of 0.74 MPa for 30 seconds. Next, a heat press was performed at 100°C and a pressure of 0.5 MPa for 60 seconds.

[0316] (6-3) Curing of resin composition Following the treatment of (6-2) above, resin sheets were laminated on both sides of the inner layer circuit board 2, and then the resin composition layer was heat cured at 130°C for 30 minutes as the first heat curing step, and then the resin composition layer was heat cured at 170°C for 30 minutes as the second heat curing step to form an insulating layer. Thereafter, the support was peeled off to expose the insulating layer. This resulted in an inner layer circuit board 2 with the insulating layer exposed (so-called "evaluation sample f").

[0317] <Evaluation of surface flatness> For each of the evaluation samples f prepared using the resin sheets of Examples 1 to 7 and Comparative Examples 1 to 5, an arbitrary 10x10 cm area on the evaluation sample f was inspected for the state of the film surface with an automatic optical inspection device (resolution 3 μm, Takano Corporation's "Hawkeyes ELITE", plain film inspection system), and the number of dents with a side of 50 μm to 150 μm that appeared in the image captured by the inspection device was counted. The evaluation results of the surface flatness are shown in Table 1 below. In Table 1 below, when the number of counted dents was 0 to 9, the surface flatness was evaluated as very high and marked with "◎", when the number was 10 to 29, the surface flatness was evaluated as high and marked with "◯", and when the number was 30 or more, the surface flatness was evaluated as low and marked with "X".

[0318] [Table 1]

Claims

1. A resin composition comprising (A) an epoxy resin, (B) a curing agent, (C) a hollow inorganic filler, and (D) an imidazole-based curing accelerator, (C) the porosity of the hollow inorganic filler is 40% by volume or more; (D) The active region of the imidazole curing accelerator includes 130° C.; The resin composition has a reaction rate of 15% or more and 70% or less after a first stage of heat curing at a curing temperature of less than 150° C., and a reaction rate of 85% or more after a second stage of heat curing at a curing temperature of 150° C. or more. Resin composition.

2. (D) The imidazole curing accelerator is represented by the formula (1): 【Chemistry 1】 [In the formula, R 1 represents a hydrogen atom or an alkyl group which may have a substituent, R 2 represents an alkyl group or a phenyl group, R 3 and R 4 each independently represents a hydrogen atom or an alkyl group. Compounds having the structure represented by The resin composition according to claim 1.

3. (D) The imidazole curing accelerator includes any one of compounds having a structure represented by formula (1-1) to formula (1-6) and an adduct of a compound having a structure represented by formula (1-7) and a compound having a structure represented by formula (2). The resin composition according to claim 1. 【Chemistry 2】 【Chemistry 3】 【Chemistry 4】 【Chemistry 5】 【Chemistry 6】 【Chemistry 7】 【Chemistry 8】 【Chemistry 9】

4. (C') further comprising a solid inorganic filler; The resin composition according to claim 1.

5. (E) further comprising a stress relief agent; The resin composition according to claim 1.

6. A sheet-like laminate material comprising a support and a resin composition layer provided on the support, the resin composition layer comprising the resin composition according to any one of claims 1 to 5.

7. A circuit board comprising a cured product of the resin composition according to any one of claims 1 to 5.

8. A semiconductor device comprising the circuit board according to claim 7.

Citation Information

Patent Citations

  • resin composition

    JP5864299B2

  • resin composition

    JP7020378B2

Cited By

  • Method for producing circuit board

    WO2026197165A1